Method for manufacturing substrate laminate and semiconductor device

By grinding and heating during the manufacturing process of the substrate laminate, the height difference between the electrode and the organic material layer is controlled, and the problem of poor conduction caused by electrode gaps during hybrid bonding is solved, thereby achieving better bonding conductivity.

CN119654696APending Publication Date: 2025-03-18MITSUI CHEMICALS INC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380056974.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-09
Filing Date
2023-07-24
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the mixed bonding of an electrode and an organic material layer containing a resin and a resin precursor, there is a problem that a gap occurs due to the height difference between the electrode and the organic material layer, resulting in poor conduction of the bonding surface.

Method used

The substrate laminated body is prepared by step A, the surface of the organic material layer is polished by step B, and the substrate laminated body after grinding is heated by step C, and the height difference between the electrode and the organic material layer is controlled to be within the range of 0.001 to 0.500 to suppress the generation of voids.

Benefits of technology

The poor conduction caused by the electrode gap during mixed bonding of the substrate laminate is effectively suppressed, and the conductivity of the bonding is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654696A_ABST
    Figure CN119654696A_ABST
Patent Text Reader

Abstract

A method for manufacturing a substrate laminate, and a semiconductor device, the method comprising: a step A in which a substrate laminate provided with a substrate, an electrode, and an organic material layer is prepared; a step B in which the surface of the substrate laminate on the side having the organic material layer is polished; and a step (C) in which the polished substrate laminate is heated. In the substrate laminate prepared in step A, an organic material layer containing a resin or the like and having a curing rate of less than 100% is provided on a surface of a substrate having an electrode. When a is the height difference between the electrode and the organic material layer in the substrate laminate before the step C is performed, b is the height difference between the electrode and the organic material layer after the step C is performed, and c is the film thickness of the organic material layer before the step C is performed, a, b, and c satisfy the following formula (1). ((b-a) / c) = 0.001 to 0.500 (1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for manufacturing a substrate stack and a semiconductor device. Background Art

[0002] With the development of small-sized, lightweight and high-performance electronic equipment, high integration of semiconductor chips, etc., with electrodes arranged on substrates, is required. However, it is difficult to fully cope with the requirements of high integration only by miniaturization of circuits. Therefore, in recent years, a method of high integration has been proposed by vertically stacking multiple semiconductor substrates (hereinafter, sometimes referred to as wafers) and semiconductor chips, etc. to form a multi-layer three-dimensional structure. As a method of stacking semiconductor substrates (wafers), semiconductor chips, etc. (hereinafter sometimes collectively referred to as "semiconductor substrates, etc."), a method of hybrid bonding using an adhesive to bond the surfaces of the substrate stack exposed with metal and insulating films to each other has been proposed (for example, refer to Japanese Patent Publication No. 4-132258, Japanese Patent Publication No. 2010-226060 and Japanese Patent Publication No. 2016-47895). Summary of the invention

[0003] Problems to be solved by the invention

[0004] In hybrid bonding of electrodes and an organic material layer including a resin and a resin precursor, there is a problem that a gap is generated between the electrodes facing each other due to the height difference between the electrodes and the organic material layer including a resin and a resin precursor, which easily causes poor conduction at the bonding surface.

[0005] An object of one embodiment of the present disclosure is to provide a method for manufacturing a substrate stack and a semiconductor device. The method for manufacturing a substrate stack can manufacture a substrate stack in which poor conduction caused by gaps between electrodes facing each other during hybrid bonding of the substrate stack is suppressed.

[0006] Solutions to Solve Problems

[0007] Specific means for solving the above-mentioned problems include the following aspects.

[0008] <1> A method for manufacturing a substrate stack, comprising: step A, preparing a substrate stack having a substrate, an electrode and an organic material layer; step B, grinding the surface of the substrate stack having the organic material layer; and step C, heating the substrate stack after grinding in step B; the organic material layer in the substrate stack prepared in step A is arranged on at least the surface of the substrate having the electrode, and the organic material layer contains a resin and a resin precursor and has a curing rate of less than 100%, and when the height difference between the electrode and the organic material layer in the substrate stack before performing step C is set to a, the height difference between the electrode and the organic material layer in the substrate stack after performing step C is set to b, and the film thickness of the organic material layer before performing step C is set to c, a, b and c satisfy the following formula (1).

[0009] [(ba) / c]=0.001~0.500 (1)

[0010] <2> like <1> The method for manufacturing a substrate laminate comprises: step D1, after performing step B, joining the substrate laminate before performing step C to a second substrate laminate having electrodes arranged on a substrate to obtain a multi-layer substrate laminate.

[0011] <3> like <1> The method for manufacturing a substrate stack includes: step D2 of bonding the first substrate stack after the step C to a second substrate stack having electrodes arranged on a substrate to obtain a multi-layer substrate stack.

[0012] <4> like <2> or <3> The method for manufacturing a substrate stack, wherein the first substrate stack and the second substrate stack have at least one insulating layer, one of the insulating layer of the first substrate stack and the insulating layer of the second substrate stack is a layer composed of an inorganic material, and at least one of the surface of the first substrate stack and the surface of the second substrate stack is an organic material layer.

[0013] <5> like <4> The method for manufacturing a substrate stack, wherein the total thickness of the organic material layers in the insulating layer of the first substrate stack and the insulating layer of the second substrate stack is greater than 1 / 20 and less than 1 / 3 relative to the total thickness of the insulating layer in the insulating layer of the first substrate stack and the insulating layer of the second substrate stack.

[0014] <6> like <4> or <5> In the method for manufacturing a substrate laminate, the insulating layer of the substrate laminate having an organic material layer on the surface thereof has a layer composed of an inorganic material.

[0015] <7> like <4> ~ <6> In any one of the methods for producing a substrate stack, at least one of a surface of the first substrate stack and a surface of the second substrate stack is a layer composed of an inorganic material, and the organic material layer is bonded to the layer composed of the inorganic material.

[0016] <8> like <4> ~ <7> The method for manufacturing a substrate stack as described in any one of the above, wherein the insulating layer of the first substrate stack is an insulating layer having a two-layer structure having a layer composed of an inorganic material and a layer of an organic material, and the first substrate stack has a first substrate, a layer composed of an inorganic material, and a layer of an organic material in sequence.

[0017] <9> like <8> In the method for manufacturing a substrate stack, the insulating layer of the second substrate stack is a layer composed of an inorganic material, that is, a single-layer insulating layer.

[0018] <10> like <2> , <4> ~ <9> The method for producing a substrate stack according to any one of the preceding claims, wherein after the step D1 is performed to obtain a multi-layer substrate stack, the multi-layer substrate stack is heated under atmospheric pressure or reduced pressure in the step C.

[0019] <11> like <2> , <4> ~ <10> The method for manufacturing a substrate stack as described in any one of the above, wherein the substrate stack is a semiconductor substrate, the second substrate stack is a semiconductor chip, the step D1 is a step of bonding two or more semiconductor chips on the semiconductor substrate to obtain a multilayer substrate stack, and after the multilayer substrate stack is obtained by implementing the step D1, the multilayer substrate stack obtained in the step D1 is heated in the step C.

[0020] <12> like <2> ~ <11> In any one of the methods for producing a substrate stack, the second substrate stack is a semiconductor chip having an electrode on one surface and an electrode on the other surface.

[0021] <13> like <2> The method for manufacturing a substrate stack, wherein the second substrate stack is a semiconductor chip, the semiconductor chip has an electrode on one surface and an electrode on the other surface,

[0022] In the step D1, two or more semiconductor chips each having an electrode on one surface and an electrode on the other surface are bonded to the substrate laminate, i.e., the semiconductor substrate, which has been polished in the step B to obtain a multilayer substrate laminate.

[0023] In the step C, the multi-layer substrate stack that has undergone the step D1 is heated, and

[0024] The method for manufacturing a substrate laminate includes performing the step D1 and the step C two or more times.

[0025] <14> like <1> ~ <13> The method for producing a substrate stack according to any one of the preceding claims, wherein a height difference between the organic material layer and the electrode in the substrate stack after the step C is performed is not less than -100 nm and not more than 200 nm.

[0026] Here, when the thickness of the electrode on the surface of the substrate having the electrode is set to b1 and the thickness of the organic material layer is set to b2, the height difference is expressed as [b1-b2], and a negative height difference indicates that the thickness of the electrode is smaller than the thickness of the organic material layer.

[0027] <15> like <1> ~ <14> The method for manufacturing a substrate stack as described in any one of the above, wherein the height difference between the organic material layer and the electrode in the substrate stack before implementing the step C is greater than -100nm and less than 0nm, and the height difference between the organic material layer and the electrode in the substrate stack after implementing the step C is greater than 0nm and less than 150nm.

[0028] Here, when the thickness of the electrode on the surface of the substrate having the electrode is set to b1 and the thickness of the organic material layer is set to b2, the height difference is expressed as [b1-b2], and a negative height difference indicates that the thickness of the electrode is smaller than the thickness of the organic material layer.

[0029] <16> like <1> ~ <15> In any one of the methods for producing a substrate laminate, in the step C, the film thickness of the organic material layer during the step C is 105% or less of the film thickness of the organic material layer before the step C is performed.

[0030] Other preferred aspects of the method for producing the substrate laminate of the present disclosure are listed below.

[0031] like <1> ~ <16> The method for producing a substrate laminate according to any one of the preceding claims, wherein a thermal linear expansion coefficient of the organic material layer in the substrate laminate in a thickness direction is not less than -10 ppm / K and not more than 150 ppm / K.

[0032] like <1> ~ <16> The method for producing a substrate laminate according to any one of the above aspects, wherein the organic material layer in the substrate laminate has a complex elastic modulus of 20 GPa or less at 23°C.

[0033] <c>like <1> ~ <16> The method for producing a substrate stack according to any one of the preceding claims, wherein the surface of the organic material layer in the substrate stack has a Si—OH group.

[0034] <d>like <1> ~ <16> The method for producing a substrate stack according to any one of the above aspects, wherein the amount of silicon on the surface of the organic material layer of the substrate stack is 0.1 atm % or more and 20 atm % or less.

[0035] <e>like <1> ~ <16> The method for producing a substrate stack according to any one of the preceding claims, wherein a ratio of the number of oxygen atoms to the number of silicon atoms (O / Si) on the surface of the organic material layer of the substrate stack is 1 or more.

[0036] <17> A semiconductor device comprises: a first substrate stack, which includes a first substrate, an electrode on the first substrate and a first insulating layer; and a second substrate stack, which includes a second substrate, an electrode on the second substrate and a second insulating layer, wherein an organic material layer is provided on one surface of the first substrate stack, and at least one of the first insulating layer and the second insulating layer is a layer composed of an inorganic material. In the insulating layers of the first substrate stack and the insulating layers of the second substrate stack, the total thickness of the organic material layers in the insulating layers including the layers composed of the inorganic material is greater than 1 / 20 and less than 1 / 3 of the total thickness of the insulating layers including the layers composed of the inorganic material, and the organic material layer serving as the first insulating layer is directly bonded to the second insulating layer.

[0037] <18> like <17> In the semiconductor device, the second insulating layer includes a layer composed of an inorganic material.

[0038] <19> like <18> In the semiconductor device, the second insulating layer includes a layer made of an inorganic material, and the layer made of the inorganic material is provided on a surface of the second substrate laminate.

[0039] <20> like <17> In the semiconductor device, the first insulating layer is an insulating layer having a two-layer structure of a layer composed of an inorganic material and an organic material layer, and the first substrate laminate has a first substrate, a layer composed of an inorganic material, and an organic material layer in this order.

[0040] <21> like <20> In the semiconductor device, the second insulating layer is a layer composed of an inorganic material, that is, a single-layer insulating layer.

[0041] <22> like <17> ~ <21> In the semiconductor device described in any one of the preceding claims, the organic material layer included in the first insulating layer includes a resin containing a siloxane bond.

[0042] Other preferred embodiments of the semiconductor device of the present disclosure are listed below.

[0043] <f>like <17> The semiconductor device described above, wherein the organic material layer included in the first insulating layer has a complex elastic modulus of 20 GPa or less at 23° C.

[0044] <g>like <17> ~ <22> The semiconductor device described in any one of the preceding claims, wherein a thermal linear expansion coefficient of the organic material layer included in the first insulating layer is greater than or equal to −10 ppm / K and less than or equal to 150 ppm / K.

[0045] <h>like <17> ~ <22> In the semiconductor device described in any one of the preceding claims, the glass transition temperature of the organic material layer included in the first insulating layer is 150° C. or higher.

[0046] like <17> ~ <22> The semiconductor device described in any one of the preceding claims, wherein the organic material layer included in the first insulating layer has a complex elastic modulus of 1 GPa or less at 200°C.

[0047] <j>like <17> ~ <22> The semiconductor device described in any one of the preceding claims, wherein, on a surface of the organic material layer included in the first insulating layer, a ratio of the number of oxygen atoms to the number of silicon atoms (O / Si) is 1 or more.

[0048] <k>like <17> ~ <22> A semiconductor device as described in any one of the preceding claims, wherein the first substrate stack has an electrode and an organic material layer as an insulating layer bonded to the second substrate stack on one side of the first substrate, and has an electrode and a layer containing an inorganic material as an insulating layer on the other side of the first substrate, the surface of the first substrate having the electrode and the organic material layer is directly bonded to the surface of the second substrate stack having the second insulating layer, the surface of the first substrate having the layer containing the inorganic material is directly bonded to the surface of a third substrate stack having the organic material layer, and the third substrate stack has an electrode and the organic material layer as a third insulating layer on one side of the third substrate.

[0049] Effects of the Invention

[0050] According to one embodiment of the present disclosure, a method for manufacturing a substrate stack and a semiconductor device can be provided. The method for manufacturing a substrate stack can manufacture a substrate stack in which poor conduction caused by gaps between electrodes facing each other during hybrid bonding of the substrate stack is suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] [< / k> < / j> < / h> < / g> < / f> < / e> < / d> < / c> Figure 1 ] is a schematic process diagram showing an example of a process for producing a substrate stack through steps A, B, and C in the method for producing a substrate stack of the present disclosure.

[0052] [ Figure 2 ] is a schematic side view showing the height difference a between the electrode and the resin in the substrate stack before implementing step C, the height difference b between the electrode and the resin in the substrate stack after implementing step C, and the film thickness c of the organic material layer before implementing step C.

[0053] [ Figure 3 ] is a schematic cross-sectional view showing an example of a state in which a substrate laminate obtained by implementing step C is joined to another laminate.

[0054] [ Figure 4 ] is a schematic cross-sectional view showing an example of a state in which a semiconductor chip having an electrode on one side is pasted on a wafer serving as a semiconductor substrate.

[0055] [ Figure 5 ] is a schematic cross-sectional view showing an example of a state in which a plurality of semiconductor chips having electrodes on one side are pasted on a wafer serving as a semiconductor substrate.

[0056] [ Fig. 6A ] is a schematic cross-sectional view showing an example of a semiconductor chip having electrodes on both sides of a substrate and having electrodes penetrating the substrate.

[0057] [ Figure 6B ] is a schematic cross-sectional view showing an example of a semiconductor chip having electrodes on both sides of a substrate and a plurality of electrodes on both sides of the substrate, wherein a portion of the electrodes are electrodes that pass through the substrate.

[0058] [ Figure 7 ] is a schematic cross-sectional view showing an example of a state in which a plurality of semiconductor chips having electrodes on both sides are pasted on a wafer serving as a semiconductor substrate.

[0059] [ Figure 8 ] is a schematic cross-sectional view showing an example of a state in which a plurality of semiconductor chips having electrodes on both sides are pasted on a wafer serving as a semiconductor substrate, and another semiconductor chip having electrodes on both sides is further stacked on the semiconductor chip.

[0060] [ Fig. 9 ] is a schematic cross-sectional view showing a substrate stack obtained by the manufacturing method of Example 3. DETAILED DESCRIPTION

[0061] In the present disclosure, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as a lower limit and an upper limit.

[0062] In the numerical range recorded in stages in the present disclosure, the upper limit or lower limit recorded in one numerical range can also be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in the present disclosure, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment.

[0063] In the present disclosure, "substrate laminate" refers to a substrate having an electrode and an organic material layer, and "multi-layer substrate laminate" refers to a substrate laminate having the following structure: a structure in which two or more substrate laminates are bonded via an insulating layer such as an organic material layer formed on a substrate by the manufacturing method of the substrate laminate of the present disclosure; or a structure in which electrodes are directly bonded to each other without passing through an organic material layer. It should be noted that the multi-layer substrate laminate may have three or more substrates, or may have a structure in which a plurality of semiconductor chips as substrates having electrodes are bonded to a substrate.

[0064] In the present disclosure, the "organic material layer" refers to a layer formed by including at least one of organic materials such as resin. Therefore, the "organic material layer" may further include inorganic materials such as inorganic fillers and inorganic pigments in addition to organic materials.

[0065] The "organic material layer" functions as an "insulating layer" in the substrate laminate. It should be noted that the "insulating layer" in the present disclosure refers to a layer with low conductivity, and the "insulating layer" may be a layer composed of an "organic material layer", a layer including an "organic material layer" and a "layer composed of an inorganic material", or a "layer composed of an inorganic material" that is not conductive.

[0066] “Layer composed of an inorganic material” refers to a layer formed of an inorganic material such as Si or SiO 2 .

[0067] In the present disclosure, "low pressure" refers to a pressure of 1 MPa or less.

[0068] The components denoted by the same reference numerals in the drawings of the present disclosure refer to the same components. The dimensions in the drawings do not necessarily represent actual dimensions, and may be expressed in an exaggerated or reduced manner as necessary.

[0069] [Method for producing substrate laminate]

[0070] The method for manufacturing a substrate laminate disclosed in the present invention comprises: step A of preparing a substrate laminate having a substrate, an electrode, and an organic material layer; step B of grinding the surface of the substrate laminate having the organic material layer; and step C of heating the substrate laminate after grinding in step B. The organic material layer in the substrate laminate prepared in step A is provided on at least the surface of the substrate having the electrode, and the organic material layer contains a resin and a resin precursor and has a curing rate of less than 100%. When the height difference between the electrode and the organic material layer in the substrate laminate before the step C is a, the height difference between the electrode and the organic material layer in the substrate laminate after the step C is b, and the film thickness of the organic material layer before the step C is c, a, b, and c satisfy the following formula (1).

[0071] [(ba) / c]=0.001~0.500 (1)

[0072] The height difference between the electrode and the resin represents [thickness of the electrode]-[thickness of the resin]. A negative height difference means that the thickness of the resin is greater than the thickness of the electrode.

[0073] In the above formula (1), if [(ba) / c] is less than 0.001, for example, in the case of a substrate laminate using copper as an electrode, due to the different thermal expansion coefficients of copper and the resin constituting the organic material layer, when there are tiny recesses in the copper, the gap between the copper joints will also become larger during the implementation of step C, and poor conductivity may sometimes occur at the copper joints.

[0074] In the above formula (1), if [(ba) / c] exceeds 0.500, for example, in a substrate laminate using copper as an electrode, the shrinkage rate of the resin film is too large, so that gaps are easily generated at the joints between the insulating films, and the conductivity of the joints may be reduced.

[0075] [(ba) / c] is 0.001 to 0.500, preferably 0.005 to 0.200, more preferably 0.005 to 0.100, further preferably 0.010 to 0.050.

[0076] Reference Figure 1 , an example of a method for manufacturing a substrate laminate of the present disclosure is described in detail.

[0077] exist Figure 1 In the method of forming an organic material layer 16 on a substrate 12 having an electrode 14 ( Figure 1 The manufacturing sequence is not limited to (A) to (B)). Figure 1 In the manner shown in the figure, the order of forming the electrode 14 and the organic material layer 16 on the substrate 12 is arbitrary. That is, as described above, step A in the present disclosure is a step of preparing a substrate laminate having an electrode and an organic material layer. For example, after forming the organic material layer 16 on the substrate 12, a groove or a hole is formed by photolithography, and an electrode is formed at least in the groove or the hole and then polished, so that the same Figure 1 (D) The same structure.

[0078] exist Figure 1 In (A), first, a substrate 12 having an electrode 14 is prepared. Next, Figure 1 As shown in (B), an organic material layer 16 is formed on one surface of the substrate 12, that is, the surface having the electrode 14. Then, step B is performed to grind the substrate laminate prepared in step A. By grinding, as shown in FIG. Figure 1 As shown in (C), the thickness of the electrode 14 and the organic material layer 16 is reduced, but the electrode 14 made of soft copper is polished more than the organic material layer 16, and a height difference may be formed after polishing.

[0079] In the method for producing a substrate stacked body of the present disclosure, in the next step C, the substrate stacked body polished in the step B is heated. Figure 1 (D) shows an example of a substrate laminate after heating. The curing of the organic material layer 16 is carried out by heating, and the formation density of the cross-linked structure becomes higher, thereby causing thermal shrinkage of the organic material layer 16, and the thickness of the organic material layer 16 becomes thinner than before heating, and sometimes the height difference between the electrode 14 and the organic material layer 16 is reduced. It should be noted that after heating in step C, step B can be performed again to grind the substrate laminate.

[0080] Figure 2 The height difference a between the electrode 14 and the organic material layer 16 in the substrate laminate before the step C in the above formula (1), the height difference b between the electrode 14 and the organic material layer 16 in the substrate laminate after the step C, and the film thickness c of the organic material layer 16 before the step C are shown. Figure 2 In the display, the height difference is magnified.

[0081] When the substrate stack 10, which is the substrate 12 having the electrode 14 and the organic material layer 16, is polished, as shown in FIG. Figure 1 As shown in (C), the electrode 14 is ground more than the organic material layer 16 to produce a height difference ( Figure 2 If the first substrate laminate 10 and the second substrate or laminate are bonded together in a state where a height difference is generated, a gap may be generated in the joint due to the height difference. If a gap is generated, the conductivity of the joint may be hindered.

[0082] In addition, below, "another substrate or laminated body", that is, another substrate or other laminated body bonded to the first substrate laminated body 10 after the step B may be referred to as "second substrate etc.".

[0083] In the method for manufacturing a substrate laminate of the present disclosure, step C is performed, that is, heating is performed before or after laminating the first substrate laminate to the second substrate etc. after performing step B. By performing step C, the reaction of the unreacted resin precursor contained in the organic material layer proceeds, curing proceeds, the crosslinking density increases, the height difference between the organic material layer and the electrode decreases, or the electrode is slightly protruded relative to the organic material layer.

[0084] This state is represented by formula (1) in the present disclosure. When the numerical value represented by the following formula (1) is in the range of 0.001 to 0.500, the generation of gaps during bonding can be effectively suppressed. As a result, the conductivity of the joint becomes better. In particular, in recent years, in order to shorten the process time by processing multiple substrates together (in batches) in an oven, direct bonding needs to be performed under low pressure, and the gaps between electrodes facing each other cannot be suppressed by pressurization. The problem of reduced conductivity caused by gaps has become significant. According to the method for manufacturing a substrate stack disclosed in the present disclosure, the reduction in conductivity caused by gaps can be suppressed even under such low pressure.

[0085] Hereinafter, the method for producing the substrate laminate of the present disclosure will be described in more detail in the order of steps with reference to examples.

[0086] <Step A of Preparing a Substrate Laminated Body Having Electrodes and an Organic Material Layer>

[0087] In step A of the method for manufacturing a substrate laminate of the present disclosure, a substrate laminate having a substrate, an electrode, and an organic material layer is prepared. Here, step A of preparing a substrate laminate having an electrode and an organic material layer includes: providing an electrode and an organic material layer on a substrate; preparing a substrate having an electrode formed in advance and providing an organic material layer; forming an organic material layer on a substrate and then forming an electrode; and purchasing a commercially available "substrate laminate having an electrode and an organic material layer". It should be noted that in the case of forming an electrode after forming an organic material layer on a substrate, other processes such as forming an electrode after forming an organic material layer on a substrate, for example, forming a hole for forming an electrode on a substrate having an organic material layer, may also be included.

[0088] In addition, when an electrode and an organic material layer are provided on a substrate in step A, the formation of the electrode on the substrate and the formation of the organic material layer can be applied by a known method.

[0089] The material of the substrate is not particularly limited, as long as it is a commonly used material. As the material of the substrate, it is preferred to include at least one element selected from the group consisting of Si, Al, Ti, Zr, Hf, Fe, Ni, Cu, Ag, Au, Ga, Ge, Sn, Pd, As, Pt, Mg, In, Ta and Nb. As the material of the substrate in step A, for example, semiconductors: Si, InP, GaN, GaAs, InGaAs, InGaAlAs, SiC, oxides, carbides, nitrides: borosilicate glass (Pyrex (registered trademark)), quartz glass (SiO2), sapphire, ZrO2, Si3N4, AlN, piezoelectrics, dielectrics: BaTiO3, LiNbO3, SrTiO3, diamond, metals: Al, Ti, Fe, Cu, Ag, Au, Pt, Pd, Ta, Nb, etc. can be cited.

[0090] As the material, a resin can be used depending on the purpose, for example, a resin selected from polydimethylsiloxane (PDMS), epoxy resin, phenol resin, polyimide, benzocyclobutene resin, polybenzoxazole, and the like.

[0091] The substrate may also be a multi-layer structure.

[0092] As the structure of the multilayer substrate, for example, there can be cited a structure in which an inorganic layer such as silicon oxide, silicon nitride, SiCN (silicon carbonitride) is formed on the surface of a silicon substrate, etc., a structure in which an organic layer such as polyimide resin, polybenzoxazole resin, imide-crosslinked siloxane resin, epoxy resin, epoxy-modified siloxane, polyparaxylene (parylene) resin, CYCLOTENE (Dow, Chem), phenolic resin is formed on the surface of a silicon substrate, etc., and a structure in which a composite of inorganic and organic substances is formed on a silicon substrate.

[0093] In addition, the multilayer substrate may include a low-k film formed by a CVD method, a sol-gel method, or an organic polymer coating method. As a film formed by a CVD method, black diamond (Applied Materials) can be cited, as a film formed by a sol-gel method, organic cross-linked siloxanes such as ethylene cross-linked siloxane and ethane cross-linked siloxane can be cited, and as a film formed by an organic polymer coating method, resins such as SiLK (trade name: Dow Chemical Company), Aurora, and fluorinated polyimide can be cited.

[0094] Furthermore, the substrate may include a photosensitive resin film such as photosensitive polyimide, photosensitive benzocyclobutene, or photosensitive CYCLOTENE.

[0095] The materials suitable for the substrate can be mainly used for the following purposes.

[0096] Substrates using Si can be used for semiconductor memories, LSI stacking, CMOS image sensors, MEMS sealing, optical devices, LEDs, and the like.

[0097] Substrates using SiO2 can be used for semiconductor memories, LSI stacking, MEMS sealing, micro-flow paths, CMOS image sensors, optical devices, LEDs, etc.

[0098] Substrates to which PDMS is applied can be used for microfluidics, etc.

[0099] Substrates using InGaAlAs, InGaAs, and InP can be used in optical devices, etc.

[0100] Substrates using InGaAlAs, GaAs, and GaN can be used for LEDs, etc.

[0101] When the electrodes are formed on the substrate in step A, the electrodes may be provided on at least one surface of the substrate or on both surfaces of the substrate. The structure in which the electrodes are provided on both surfaces of the substrate will be described later.

[0102] The electrode may be formed in a protruding shape on the surface of the substrate, may be formed in a state of penetrating the substrate, or may be formed in a state of being buried in the substrate.

[0103] As described later, in a substrate having an electrode on one surface, since an organic material layer is formed on the surface of the substrate having the electrode, the electrode is preferably formed in a convex shape on the surface of the substrate.

[0104] Examples of the material of the electrode include copper, solder, tin, gold, silver, aluminum, cobalt, and ruthenium.

[0105] When forming the electrode on the substrate, examples of a method for forming the electrode include electroplating, chemical plating, sputtering, and an inkjet method.

[0106] The thickness of the substrate is appropriately selected depending on the purpose, and is preferably 0.5 μm to 1 mm, more preferably 1 μm to 900 μm, and even more preferably 2 μm to 900 μm.

[0107] The shape of the substrate is not particularly limited. For example, when the substrate is a silicon substrate, it may be a silicon substrate formed with an interlayer insulating layer (Low-k film), and fine grooves (recesses), fine through holes, etc. may be formed in the silicon substrate.

[0108] There is no particular restriction on the surface roughness (Ra) of the insulating layer of the bonding surface. From the perspective of facilitating temporary fixation at low temperature when bonding a substrate having electrodes to another substrate having electrodes, the surface roughness (Ra) of the insulating layer of the bonding surface is preferably less than 1.2 nm.

[0109] The surface roughness of the substrate can be evaluated by morphological observation using a scanning probe microscope (SPM). Specifically, the surface roughness is determined by measuring a 3 μm×3 μm square area using a SPM such as SPA400 (manufactured by Hitachi High-Technologies Corporation) in a dynamic force microscope mode.

[0110] The water droplet contact angle on the surface of the substrate is preferably independently less than 90°. From the perspective of being able to temporarily fix a substrate with electrodes formed thereon at a low temperature when joining it to another substrate with electrodes formed thereon, the water droplet contact angle on the surface of the substrate is more preferably less than 90°.

[0111] Specifically, the water drop contact angle was determined by measuring the static contact angle of water at 23° C. and a humidity of 50% using a solid-liquid interface analysis system (Drop Master 500 Image Processing System, manufactured by Kyowa Interface Science Co., Ltd.).

[0112] Figure 1 (A) is a schematic cross-sectional view showing a substrate on which electrodes prepared in step A are arranged. Figure 1 In the example shown in (A), an electrode 14 is provided on one surface of a substrate 12 .

[0113] Step A may include a step of providing an organic material layer containing a resin and a resin precursor and having a curing rate of less than 100% on at least the surface of the substrate having the electrode to form a substrate laminate.

[0114] For example, Figure 1 (B) shows a state where the organic material layer 16 is provided on the surface of the substrate 12 on the side where the electrode 14 is provided.

[0115] (Organic material layer)

[0116] The organic material layer is not particularly limited as long as it contains a resin and a resin precursor that are cured by heating and can shrink by heating.

[0117] Examples of materials for forming the organic material layer include: materials that form bonds or structures such as polyimide, polyamide, polyamideimide, polyparaxylene, polyarylene ether, tetralin, and octahydroanthracene by cross-linking; materials that form nitrogen-containing ring structures such as polybenzoxazole and polybenzoxazine; materials that form bonds or structures such as Si-O by cross-linking; and organic materials such as siloxane-modified compounds.

[0118] The organic material may also contain an aromatic ring structure. In addition, the resin material may include a polymerizable compound that can be homopolymerized or copolymerized, a combination of the polymerizable compound and a crosslinking agent, etc. In addition, the material forming the organic material layer may also be a photosensitive material, i.e., a photocurable material.

[0119] Examples of the structure having a Si—O bond (siloxane bond) include structures represented by the following formulae (1) to (3).

[0120] [Chemistry 1]

[0121]

[0122] In the structure having Si-O bond (siloxane bond), the group bonded to Si may be substituted by an alkylene group, a phenylene group, or the like. For example, it may be a group having (-O-) x (R1) y Si-(R2)-Si(R1) y (-O-) x The structure of (R1 represents a methyl group, etc., R2 represents an alkylene group, a phenylene group, etc. x and y are each independently an integer greater than 0, and x+y is 3).

[0123] As materials that form Si-O bonds by crosslinking, for example, compounds represented by the following formulae (4) and (5) can be cited. In addition, the structures represented by formulae (1) and (2) can be generated, for example, by heating the compounds represented by formulae (4) and (5) to react.

[0124] [Chemistry 2]

[0125]

[0126] For example, when the material contained in the organic material layer includes a material that forms a bond or structure such as polyimide, polyamide, or polyamideimide by cross-linking, it preferably includes the following compound (A) and a cross-linking agent (B), wherein the compound (A) has a cationic functional group containing at least one of a primary nitrogen atom and a secondary nitrogen atom, and has a weight-average molecular weight of 900,000 to 400,000; the cross-linking agent (B) has 3 or more -C(=O)OX groups (X is a hydrogen atom or an alkyl group having 1 to 6 carbon atoms) in the molecule, and 1 or more and 6 or less of the 3 or more -C(=O)OX groups are -C(=O)OH groups, and has a weight-average molecular weight of 200 to 600.

[0127] (Compound (A))

[0128] Compound (A) is a compound having a cationic functional group containing at least one of a primary nitrogen atom and a secondary nitrogen atom and having a weight average molecular weight of 90 to 400,000. The cationic functional group is not particularly limited as long as it is a functional group that can be positively charged and contains at least one of a primary nitrogen atom and a secondary nitrogen atom.

[0129] Furthermore, the compound (A) may contain a tertiary nitrogen atom in addition to the primary nitrogen atom and the secondary nitrogen atom.

[0130] In the present disclosure, a "primary nitrogen atom" refers to a nitrogen atom bonded only to two hydrogen atoms and one atom other than hydrogen atoms (e.g., a nitrogen atom contained in a primary amino group (-NH2 group)), or a nitrogen atom bonded only to three hydrogen atoms and one atom other than hydrogen atoms (cation).

[0131] In addition, a "secondary nitrogen atom" refers to a nitrogen atom bonded to only one hydrogen atom and two atoms other than a hydrogen atom (i.e., a nitrogen atom contained in a functional group represented by the following formula (a)), or a nitrogen atom bonded to only two hydrogen atoms and two atoms other than a hydrogen atom (cation).

[0132] In addition, a "tertiary nitrogen atom" refers to a nitrogen atom bonded to only three atoms other than a hydrogen atom (i.e., a nitrogen atom as a functional group represented by the following formula (b)), or a nitrogen atom bonded to only one hydrogen atom and three atoms other than a hydrogen atom (cation).

[0133] [Chemistry 3]

[0134]

[0135] In formula (a) and formula (b), * represents a bonding position to an atom other than a hydrogen atom.

[0136] Here, the functional group represented by the formula (a) may be a secondary amino group (-NHR a Here, R a The functional group representing a part of an alkyl group may be a divalent linking group contained in the polymer skeleton.

[0137] In addition, the functional group represented by the formula (b) (ie, the tertiary nitrogen atom) may be a tertiary amino group (-NR b R c Here, R b and R c The functional groups each independently represent a part of an alkyl group) may be a trivalent linking group contained in the polymer skeleton.

[0138] The weight average molecular weight of the compound (A) is 90 or more and 400,000 or less.

[0139] As compound (A), for example, aliphatic amines, compounds having a siloxane bond (Si-O bond) and an amino group, amine compounds having a ring structure without a Si-O bond in the molecule, etc. can be cited. When compound (A) is an aliphatic amine, the weight average molecular weight is preferably 10,000 or more and 200,000 or less. When compound (A) is a compound having a siloxane bond (Si-O bond) and an amino group, the weight average molecular weight is preferably 130 or more and 10,000 or less, more preferably 130 or more and 5,000 or less, and further preferably 130 or more and 2,000 or less. When compound (A) is an amine compound having a ring structure without a Si-O bond in the molecule, the weight average molecular weight is preferably 90 or more and 600 or less.

[0140] In addition, in this disclosure, the weight average molecular weight means the weight average molecular weight of polyethylene glycol conversion measured by GPC (gel permeation chromatography) method for things other than monomers.

[0141] Specifically, the weight-average molecular weight is calculated as follows: an aqueous solution with a sodium nitrate concentration of 0.1 mol / L is used as a developing solvent, an analytical device Shodex DET RI-101 and two analytical columns (TSKgel G6000 PWXL-CP and TSKgel G3000 PWXL-CP manufactured by Tosoh) are used to detect the refractive index at a flow rate of 1.0 mL / min, and polyethylene glycol / polyethylene oxide are used as standard products, and calculation is performed using analytical software (Empower3 manufactured by Waters).

[0142] In addition, the compound (A) may further have an anionic functional group, a nonionic functional group, etc. as necessary.

[0143] The nonionic functional group may be a hydrogen bond acceptor group or a hydrogen bond donor group. Examples of the nonionic functional group include a hydroxyl group, a carbonyl group, and an ether group (—O—).

[0144] The anionic functional group is not particularly limited as long as it is a functional group that can carry a negative charge. Examples of the anionic functional group include a carboxylic acid group, a sulfonic acid group, and a sulfate group.

[0145] Examples of the compound (A) include aliphatic amines, and more specifically, polymers of alkyleneimines such as ethyleneimine, propyleneimine, butyleneimine, pentyleneimine, hexyleneimine, heptyleneimine, octyleneimine, trimethyleneimine, tetramethyleneimine, pentamethyleneimine, hexamethyleneimine, and octamethyleneimine, i.e., polyalkyleneimines; polyallylamine; and polyacrylamide.

[0146] Polyethyleneimine (PEI) can be produced by a known method described in Japanese Patent Publication No. 43-8828, Japanese Patent Publication No. 49-33120, Japanese Patent Publication No. 2001-213958, International Publication No. 2010 / 137711, etc. Polyalkyleneimines other than polyethyleneimine can also be produced by the same method as polyethyleneimine.

[0147] Compound (A) is also preferably a derivative of the above-mentioned polyalkyleneimine (polyalkyleneimine derivative; particularly preferably polyethyleneimine derivative). As the polyalkyleneimine derivative, there is no particular limitation as long as it is a compound that can be produced using the above-mentioned polyalkyleneimine. Specifically, there can be mentioned polyalkyleneimine derivatives in which an alkyl group (preferably an alkyl group having 1 to 10 carbon atoms), an aryl group, etc. are introduced into the polyalkyleneimine, and polyalkyleneimine derivatives obtained by introducing a crosslinking group such as a hydroxyl group into the polyalkyleneimine.

[0148] These polyalkyleneimine derivatives can be produced by a commonly used method using the above-mentioned polyalkyleneimine, and specifically, can be produced according to the method described in, for example, Japanese Patent Application Laid-Open No. 6-016809.

[0149] Furthermore, as the polyalkyleneimine derivative, highly branched polyalkyleneimine obtained by reacting a cationic functional group-containing monomer with polyalkyleneimine to increase the branching degree of polyalkyleneimine is also preferred.

[0150] As methods for obtaining highly branched polyalkyleneimine, for example, there can be mentioned: a method in which a monomer containing a cationic functional group is reacted with a polyalkyleneimine having a plurality of secondary nitrogen atoms in the skeleton to replace at least one of the plurality of secondary nitrogen atoms with the monomer containing a cationic functional group; a method in which a monomer containing a cationic functional group is reacted with a polyalkyleneimine having a plurality of primary nitrogen atoms at the terminal to replace at least one of the plurality of primary nitrogen atoms with the monomer containing a cationic functional group, etc.

[0151] Examples of the cationic functional group introduced to increase the degree of branching include aminoethyl, aminopropyl, diaminopropyl, aminobutyl, diaminobutyl, triaminobutyl and the like. From the perspective of reducing the cationic functional group equivalent and increasing the cationic functional group density, the aminoethyl group is preferred.

[0152] The polyethyleneimine and its derivatives may be commercially available products. Examples of commercially available products include polyethyleneimine and its derivatives commercially available from Nippon Shokubai Co., Ltd., BASF Corporation, MP-Biomedicals Corporation, etc., and they may be appropriately selected and used.

[0153] As compound (A), in addition to the above-mentioned aliphatic amines, compounds having Si-O bonds and amino groups can be cited. As compounds having Si-O bonds and amino groups, for example, siloxane diamine, silane coupling agents having amino groups, siloxane polymers of silane coupling agents having amino groups, etc. can be cited.

[0154] As a silane coupling agent which has an amino group, the compound represented by following formula (A-3) is mentioned, for example.

[0155] [Chemistry 4]

[0156]

[0157] In formula (A-3), R 1 represents an alkyl group having 1 to 4 carbon atoms which may be substituted. 2 and R 3 Each independently represents an alkylene group having 1 to 12 carbon atoms, an ether group or a carbonyl group which may be substituted (a carbonyl group, an ether group or the like may be contained in the skeleton). 4 and R 5 Each independently represents an alkylene group having 1 to 4 carbon atoms which may be substituted or a single bond. Ar represents a divalent or trivalent aromatic ring. 1 represents hydrogen or an optionally substituted alkyl group having 1 to 5 carbon atoms. 2 represents hydrogen, a cycloalkyl group, a heterocyclic group, an aryl group, or an alkyl group having 1 to 5 carbon atoms which may be substituted (a carbonyl group, an ether group, etc. may be included in the skeleton). 1 , R 2 , R 3 , R 4 , R 5 , X 1 Can be the same or different.

[0158] As R 1 , R 2 , R 3 , R 4 , R 5 , X 1 , X 2 The substituents of the alkyl group and the alkylene group in the above-mentioned group may be amino, hydroxyl, alkoxy, cyano, carboxylic acid, sulfonic acid, halogen or the like, each independently mentioned.

[0159] Examples of the divalent or trivalent aromatic ring in Ar include a divalent or trivalent benzene ring. 2 Examples of the aryl group include phenyl, methylbenzyl and vinylbenzyl.

[0160] Specific examples of the silane coupling agent represented by formula (A-3) include N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminoisobutyldimethylmethoxysilane, N-(2-aminoethyl)-3-aminoisobutylmethyldimethoxysilane, N-(2-aminoethyl)-11-aminoundecyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, (aminoethylaminoethyl)phenyltriethoxysilane, methylbenzylaminoethylaminopropyltrimethoxysilane, benzylaminoethylaminopropyltriethoxysilane, and 3-ureidopropyltriethoxysilane. , (aminoethylaminoethyl)phenethyltrimethoxysilane, (aminoethylaminomethyl)phenethyltrimethoxysilane, N-[2-[3-(trimethoxysilyl)propylamino]ethyl]ethylenediamine, 3-aminopropyldiethoxymethylsilane, 3-aminopropyldimethoxymethylsilane, 3-aminopropyldimethylethoxysilane, 3-aminopropyldimethylmethoxysilane, trimethoxy[2-(2-aminoethyl)-3-aminopropyl]silane, diaminomethylmethyldiethoxysilane, methylaminomethylmethyldiethoxysilane, p-aminophenyltrimethoxysilane, N-methylaminopropyltriethoxysilane, N-methylaminopropylmethyldiethoxysilane, (phenylaminomethyl)methyldiethoxysilane, acetamidopropyltrimethoxysilane and their hydrolyzates.

[0161] Examples of the amino group-containing silane coupling agent other than that represented by formula (A-3) include N,N-bis[3-(trimethoxysilyl)propyl]ethylenediamine, N,N′-bis[3-(trimethoxysilyl)propyl]ethylenediamine, bis[(3-triethoxysilyl)propyl]amine, piperazinylpropylmethyldimethoxysilane, bis[3-(triethoxysilyl)propyl]urea, bis(methyldiethoxysilylpropyl)amine, 2,2-dimethoxy-1,6-diaza-2-silacyclooctane, 3,5-diamino-N-(4-(methoxydimethylsilyl)phenyl)benzamide, 3,5-diamino-N-(4-(triethoxysilyl)phenyl)benzamide, 5-(ethoxydimethylsilyl)benzene-1,3-diamine, and hydrolyzates thereof.

[0162] The silane coupling agent with amino group can be used alone or in combination of two or more. In addition, a silane coupling agent with amino group and a silane coupling agent without amino group can also be used in combination. For example, in order to improve the adhesion with metal, a silane coupling agent with mercapto group can be used.

[0163] In addition, polymers (siloxane polymers) formed by these silane coupling agents via siloxane bonds (Si-O-Si) can also be used. For example, polymers having a linear siloxane structure, polymers having a branched siloxane structure, polymers having a cyclic siloxane structure, polymers having a caged siloxane structure, etc. can be obtained from the hydrolyzate of 3-aminopropyltrimethoxysilane. The caged siloxane structure is represented by the following formula (A-1), for example.

[0164] [Chemistry 5]

[0165]

[0166] Examples of the siloxane diamine include compounds represented by the following formula (A-2): In the formula (A-2), i is an integer of 0 to 4, j is an integer of 1 to 3, and Me is a methyl group.

[0167] [Chemistry 6]

[0168]

[0169] Examples of the siloxane diamine include 1,3-bis(3-aminopropyl)tetramethyldisiloxane (in formula (A-2), i=0, j=1) and 1,3-bis(2-aminoethylamino)propyltetramethyldisiloxane (in formula (A-2), i=1, j=1).

[0170] As compound (A), in addition to the aliphatic amine and the compound having Si-O bond and amino group, there can be mentioned an amine compound having no Si-O bond in the molecule but a ring structure. Among them, it is preferred that the amine compound having no Si-O bond in the molecule but a ring structure has a weight average molecular weight of more than 90 and less than 600. As the amine compound having no Si-O bond in the molecule but a ring structure with a weight average molecular weight of more than 90 and less than 600, alicyclic amines, aromatic ring amines, heterocyclic amines, etc. can be mentioned. There can be multiple ring structures in the molecule, and the multiple ring structures can be the same or different. As the amine compound having a ring structure, since a more thermally stable compound can be easily obtained, a compound having an aromatic ring is more preferred.

[0171] In addition, as the amine compound having a weight average molecular weight of 90 to 600 having no Si-O bond in the molecule and having a ring structure, a compound having a primary amino group is preferred from the viewpoint that it is easy to form a thermal crosslinking structure such as amide, amideimide, or imide together with the crosslinking agent (B) and can improve the heat resistance. Furthermore, as the amine compound, a diamine compound having two primary amino groups, a triamine compound having three primary amino groups, etc. are preferred from the viewpoint that it is easy to increase the number of thermal crosslinking structures such as amide, amideimide, or imide together with the crosslinking agent (B) and can further improve the heat resistance.

[0172] Examples of the alicyclic amine include cyclohexylamine and dimethylaminocyclohexane.

[0173] Examples of the aromatic cyclic amine include diaminodiphenyl ether, xylylenediamine (preferably p-xylylenediamine), diaminobenzene, diaminotoluene, methylenedianiline, dimethyldiaminobiphenyl, bis(trifluoromethyl)diaminobiphenyl, diaminobenzophenone, diaminobenzanilide, bis(aminophenyl)fluorene, bis(aminophenoxy)benzene, bis(aminophenoxy)biphenyl, dicarboxydiaminodiphenylmethane, diaminoresorcinol, dihydroxybenzidine, diaminobenzidine, 1,3,5-triaminophenoxybenzene, 2,2'-dimethylbenzidine, tris(4-aminophenyl)amine, 2,7-diaminofluorene, 1,9-diaminofluorene, and dibenzylamine.

[0174] Examples of the heterocyclic ring of the heterocyclic amine include a heterocyclic ring containing a sulfur atom as a heteroatom (e.g., a thiophene ring), or a heterocyclic ring containing a nitrogen atom as a heteroatom (e.g., a 5-membered ring such as a pyrrole ring, a pyrrolidine ring, a pyrazole ring, an imidazole ring, and a triazole ring; a 6-membered ring such as an isocyanurate ring, a pyridine ring, a pyridazine ring, a pyrimidine ring, a pyrazine ring, a piperidine ring, a piperazine ring, and a triazine ring; and a condensed ring such as an indole ring, an indoleline ring, a quinoline ring, an acridine ring, a naphthyridine ring, a quinazoline ring, a purine ring, and a quinoxaline ring).

[0175] For example, examples of the heterocyclic amine having a nitrogen-containing heterocyclic ring include melamine, ammeline, melam, melem, and tris(4-aminophenyl)amine.

[0176] Furthermore, examples of the amine compound having both a heterocyclic ring and an aromatic ring include N2,N4,N6-tris(4-aminophenyl)-1,3,5-triazine-2,4,6-triamine and the like.

[0177] Since compound (A) has a primary or secondary amino group, it can firmly bond the substrates to each other through electrostatic interaction with functional groups such as hydroxyl, epoxy, carboxyl, amino, and mercapto groups that may exist on the surfaces of the first and second substrates, or by tightly forming covalent bonds with the functional groups.

[0178] In addition, since the compound (A) has a primary or secondary amino group, it is easily soluble in the polar solvent (D) described later. By using a compound (A) that is easily soluble in a polar solvent (D), the affinity with the hydrophilic surface of a substrate such as a silicon substrate becomes higher, so it is easy to form a smooth film, and the thickness of the joint portion where a plurality of substrate stacks are mixed and joined can be reduced.

[0179] As the compound (A), from the viewpoint of forming a smooth thin film, an aliphatic amine or a compound having a Si—O bond and an amino group is preferred, and from the viewpoint of heat resistance, a compound having a Si—O bond and an amino group is more preferred.

[0180] When compound (A) contains a compound having a Si-O bond and an amino group, it is preferred from the perspective of forming a smooth film if the ratio of the total number of primary nitrogen atoms and secondary nitrogen atoms in compound (A) to the number of silicon atoms (total number of primary nitrogen atoms and secondary nitrogen atoms / number of silicon atoms) is greater than 0.2 and less than 5.

[0181] When compound (A) includes a compound having a Si-O bond and an amino group, from the aspect of adhesion between substrates, in the compound having a Si-O bond and an amino group, it is preferred that the non-crosslinking group such as a methyl group bonded to Si satisfies the relationship (non-crosslinking group) / Si<2 in terms of molar ratio. It is inferred that by satisfying this relationship, the crosslinking density (crosslinking of Si-O-Si bonds with amide bonds, imide bonds, etc.) of the formed film is increased, the substrates have sufficient adhesion to each other, and the peeling of the substrates can be suppressed.

[0182] As described above, compound (A) has a cationic functional group containing at least one of a primary nitrogen atom and a secondary nitrogen atom. Here, when compound (A) contains a primary nitrogen atom, the proportion of the primary nitrogen atom in all nitrogen atoms in compound (A) is preferably 20 mol% or more, more preferably 25 mol% or more, and further preferably 30 mol% or more. In addition, compound (A) may have a cationic functional group containing a primary nitrogen atom and not containing a nitrogen atom other than a primary nitrogen atom (e.g., a secondary nitrogen atom, a tertiary nitrogen atom).

[0183] When compound (A) contains secondary nitrogen atoms, the ratio of the secondary nitrogen atoms to all nitrogen atoms in compound (A) is preferably 5 mol% to 50 mol%, more preferably 10 mol% to 45 mol%.

[0184] In addition, compound (A) may contain tertiary nitrogen atoms in addition to primary nitrogen atoms and secondary nitrogen atoms. When compound (A) contains tertiary nitrogen atoms, the proportion of tertiary nitrogen atoms in all nitrogen atoms in compound (A) is preferably greater than 20 mol% and less than 50 mol%, and more preferably greater than 25 mol% and less than 45 mol%.

[0185] In the present disclosure, the content of the component derived from compound (A) in the joint is not particularly limited, and can be, for example, 1% by mass or more and 82% by mass or less, preferably 5% by mass or more and 82% by mass or less, and more preferably 13% by mass or more and 82% by mass or less, relative to the entire joint.

[0186] (Crosslinking agent (B))

[0187] The crosslinking agent (B) is a compound having three or more -C(=O)OX groups (X is a hydrogen atom or an alkyl group having 1 to 6 carbon atoms) in the molecule, one or more and six or less of the three or more -C(=O)OX groups (hereinafter also referred to as "COOX") are -C(=O)OH groups (hereinafter also referred to as "COOH"), and having a weight average molecular weight of 200 to 600.

[0188] The crosslinking agent (B) is a compound having 3 or more -C(=O)OX groups (X is a hydrogen atom or an alkyl group having 1 to 6 carbon atoms) in the molecule, preferably a compound having 3 or more to 6 -C(=O)OX groups in the molecule, and more preferably a compound having 3 or 4 -C(=O)OX groups in the molecule.

[0189] In the crosslinking agent (B), X in the -C(=O)OX group may be a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and preferably a hydrogen atom, a methyl group, an ethyl group, or a propyl group. It should be noted that X in the -C(=O)OX group may be the same or different.

[0190] The crosslinking agent (B) is a compound having 1 or more and 6 or less -C(=O)OH groups in which X is a hydrogen atom in the molecule, preferably a compound having 1 or more and 4 or less -C(=O)OH groups in the molecule, more preferably a compound having 2 or more and 4 or less -C(=O)OH groups in the molecule, and further preferably a compound having 2 or 3 -C(=O)OH groups in the molecule.

[0191] The crosslinking agent (B) is a compound having a weight average molecular weight of 200 or more and 600 or less. Preferably, it is a compound having a weight average molecular weight of 200 or more and 400 or less.

[0192] The crosslinking agent (B) preferably has a ring structure in the molecule. Examples of the ring structure include an alicyclic structure, an aromatic ring structure, etc. In addition, the crosslinking agent (B) may also have multiple ring structures in the molecule, and the multiple ring structures may be the same or different.

[0193] Examples of the alicyclic structure include an alicyclic structure having 3 to 8 carbon atoms, preferably an alicyclic structure having 4 to 6 carbon atoms, and the ring structure may be saturated or unsaturated. More specifically, examples of the alicyclic structure include saturated alicyclic structures such as a cyclopropane ring, a cyclobutane ring, a cyclopentane ring, a cyclohexane ring, a cycloheptane ring, and a cyclooctane ring; and unsaturated alicyclic structures such as a cyclopropene ring, a cyclobutene ring, a cyclopentene ring, a cyclohexene ring, a cycloheptene ring, and a cyclooctene ring.

[0194] The aromatic ring structure is not particularly limited as long as it is a ring structure showing aromaticity, and examples thereof include benzene-based aromatic rings such as benzene ring, naphthalene ring, anthracene ring, and perylene ring, aromatic heterocyclic rings such as pyridine ring and thiophene ring, and non-benzene-based aromatic rings such as indene ring and azulene ring.

[0195] The ring structure of the crosslinking agent (B) in the molecule is preferably at least one selected from the group consisting of a cyclobutane ring, a cyclopentane ring, a cyclohexane ring, a benzene ring and a naphthalene ring. From the perspective of further improving the heat resistance of the bonded portion, at least one of a benzene ring and a naphthalene ring is more preferred.

[0196] As described above, the crosslinking agent (B) may have a plurality of ring structures in the molecule, and when the ring structure is benzene, the crosslinking agent (B) may have a biphenyl structure, a benzophenone structure, a diphenyl ether structure, or the like.

[0197] The crosslinking agent (B) preferably has a fluorine atom in the molecule, more preferably has 1 or more and 6 or less fluorine atoms in the molecule, and further preferably has 3 or more and 6 or less fluorine atoms in the molecule. For example, the crosslinking agent (B) may have a fluoroalkyl group in the molecule, specifically, a trifluoroalkyl group or a hexafluoroisopropyl group.

[0198] In addition, examples of the crosslinking agent (B) include carboxylic acid compounds such as alicyclic carboxylic acids, benzene carboxylic acids, naphthalene carboxylic acids, diphthalic acids, and fluorinated aromatic ring carboxylic acids; and carboxylate compounds such as alicyclic carboxylic acid esters, benzene carboxylic acid esters, naphthalene carboxylic acid esters, diphthalic acid esters, and fluorinated aromatic ring carboxylic acid esters. It should be noted that the carboxylate compound is a compound having a carboxyl group (-C(=O)OH group) in the molecule, and at least one X among three or more -C(=O)OX groups is an alkyl group having a carbon number of 1 or more and 6 or less (i.e., having an ester bond). In the present disclosure, by making the crosslinking agent (B) a carboxylate compound, the aggregation caused by the association of the compound (A) and the crosslinking agent (B) can be suppressed, the number of aggregates and pits is reduced, and the adjustment of the film thickness becomes easy.

[0199] The carboxylic acid compound is preferably a 4-valent or less carboxylic acid compound containing 4 or less -C(=O)OH groups, and more preferably a 3- or 4-valent carboxylic acid compound containing 3 or 4 -C(=O)OH groups.

[0200] The carboxylic acid ester compound is preferably a compound containing 3 or less carboxyl groups (—C(═O)OH groups) and 3 or less ester bonds in the molecule, and more preferably a compound containing 2 or less carboxyl groups and 2 or less ester bonds in the molecule.

[0201] In the carboxylate compound, when X is an alkyl group having 1 to 6 carbon atoms among the three or more -C(=O)OX groups, X is preferably a methyl group, an ethyl group, a propyl group, a butyl group, etc., and is preferably an ethyl group or a propyl group from the viewpoint of further suppressing the aggregation caused by the association of the compound (A) and the crosslinking agent (B).

[0202] Specific examples of the carboxylic acid compound include, but are not limited to, alicyclic carboxylic acids such as 1,2,3,4-cyclobutanetetracarboxylic acid, 1,2,3,4-cyclopentanetetracarboxylic acid, 1,3,5-cyclohexanetricarboxylic acid, 1,2,4-cyclohexanetricarboxylic acid, 1,2,4,5-cyclohexanetetracarboxylic acid, and 1,2,3,4,5,6-cyclohexanehexacarboxylic acid; phenylcarboxylic acids such as 1,2,4-benzenetricarboxylic acid, 1,3,5-benzenetricarboxylic acid, pyromellitic acid, benzenepentacarboxylic acid, and benzenehexacarboxylic acid; naphthalenetetracarboxylic acid such as 1,4,5,8-naphthalenetetracarboxylic acid, 2,3,6,7-naphthalenetetracarboxylic acid, and the like. Carboxylic acids; 3,3',5,5'-tetracarboxydiphenylmethane, biphenyl-3,3',5,5'-tetracarboxylic acid, biphenyl-3,4',5-tricarboxylic acid, biphenyl-3,3',4,4'-tetracarboxylic acid, benzophenone-3,3',4,4'-tetracarboxylic acid, 4,4'-oxydiphthalic acid, 3,4'-oxydiphthalic acid, 1,3-bis(phthalic acid)tetramethyldisiloxane, 4,4'-(ethynyl-1,2-diyl)diphthalic acid acid), 4,4'-(1,4-phenylenebis(oxy))diphthalic acid), 4,4'-([1,1'-biphenyl]-4,4'-diylbis(oxy))diphthalic acid), 4,4'-((oxybis(4,1-phenylene))bis(oxy))diphthalic acid acid) and other diphthalic acids; perylene-3,4,9,10-tetracarboxylic acid and other perylene carboxylic acids; anthracene-2,3,6,7-tetracarboxylic acid and other anthracene carboxylic acids; fluorinated aromatic ring carboxylic acids such as 4,4'-(hexafluoroisopropylidene)diphthalic acid, 9,9-bis(trifluoromethyl)-9H-xanthene-2,3,6,7-tetracarboxylic acid and 1,4-bis(trifluoromethyl)pyromellitic acid.

[0203] Specific examples of the carboxylic acid ester compound include compounds in which at least one carboxyl group in the specific examples of the carboxylic acid compound is substituted with an ester group. Examples of the carboxylic acid ester compound include half-esterified compounds represented by the following general formulas (B-1) to (B-5).

[0204] [Chemistry 7]

[0205]

[0206] R in general formulae (B-1) to (B-5) is independently an alkyl group having 1 to 6 carbon atoms, preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and more preferably an ethyl group or a propyl group.

[0207] Y in the general formula (B-2) is a single bond, O, C=O, or C(CF3)2, and is preferably O.

[0208] The half-esterified compound can be produced by, for example, mixing carboxylic acid anhydride, which is the anhydride of the carboxylic acid compound, with an alcohol solvent and ring-opening the carboxylic acid anhydride.

[0209] In the present disclosure, the content of the component derived from the crosslinking agent (B) in the organic material layer is not particularly limited. For example, the ratio of the number of carbonyl groups (-(C=O)-Y) in the substance derived from the crosslinking agent (B) to the number of all nitrogen atoms in the substance derived from the compound (A) ((-(C=O)-Y) / N) is preferably greater than 0.1 and less than 3.0, more preferably greater than 0.3 and less than 2.5, and further preferably greater than 0.4 and less than 2.2. Here, in -(C=O)-Y, Y represents a nitrogen atom, OH or ester group crosslinked by imide or amide. By making (-(C=O)-Y) / N greater than 0.1 and less than 3.0, the joint portion appropriately has a crosslinked structure such as amide, amideimide, imide, and the heat resistance is better.

[0210] It is believed that since compound (A) has an uncrosslinked cationic functional group, when compound (A) is included as a component of the junction and crosslinking agent (B) is not included, the crosslinking density is low and the heat resistance is insufficient. On the other hand, in the organic material layer, the cationic functional group of compound (A) reacts with the carboxyl group of the crosslinking agent (B) to form a covalent bond, thereby increasing the crosslinking density and having high heat resistance.

[0211] (Polar solvent (D))

[0212] In step B, a solution containing an organic material such as a resin may be applied to at least one surface of the substrate to form an organic material layer. The solution containing an organic material (hereinafter, also referred to as a composition for forming an organic material layer) preferably contains a polar solvent (D) in addition to the organic material such as the compound (A) and the crosslinking agent (B). Here, the polar solvent (D) refers to a solvent having a relative dielectric constant of 5 or more at room temperature (25° C.).

[0213] Examples of the polar solvent (D) include, specifically, protic inorganic compounds such as water and heavy water; alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, isopentanol, cyclohexanol, ethylene glycol, propylene glycol, 2-methoxyethanol, 2-ethoxyethanol, benzyl alcohol, diethylene glycol, triethylene glycol, and glycerol; ethers such as tetrahydrofuran and dimethoxyethane; aldehydes / ketones such as furfural, acetone, methyl ethyl ketone, and cyclohexane; acid derivatives such as acetic anhydride, ethyl acetate, butyl acetate, ethylene carbonate, propylene carbonate, formaldehyde, N-methylformamide, N,N-dimethylformamide, N-methylacetamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, and hexamethylphosphoramide; nitriles such as acetonitrile and propionitrile; nitro compounds such as nitromethane and nitrobenzene; and sulfur compounds such as dimethyl sulfoxide. As the polar solvent (D), a protic solvent is preferably contained, water is more preferably contained, and ultrapure water is further preferably contained.

[0214] The content of the polar solvent (D) in the solution is not particularly limited, and is, for example, 1.0% by mass or more and 99.99896% by mass or less, and preferably 40% by mass or more and 99.99896% by mass or less, based on the entire solution.

[0215] From the viewpoint of volatilizing the polar solvent (D) by heating during formation of the organic material layer and reducing the amount of residual solvent in the organic material layer, the boiling point of the polar solvent (D) is preferably 150° C. or lower, more preferably 120° C. or lower.

[0216] (Additive (C))

[0217] The composition for forming an organic material layer containing an organic material may further contain an additive (C) in addition to the organic materials such as the compound (A), the crosslinking agent (B), and the polar solvent. As the additive (C), an acid (C-1) having a weight average molecular weight of 46 or more and 195 or less having a carboxyl group and a base (C-2) having a weight average molecular weight of 17 or more and 120 or less having a nitrogen atom and not having a ring structure may be cited. In addition, although the additive (C) is volatilized by heating when forming the joint portion, the joint portion in the substrate laminate of the present disclosure may contain the additive (C).

[0218] Acid (C-1) is an acid having a weight average molecular weight of 46 or more and 195 or less having a carboxyl group. It is speculated that by including acid (C-1) as an additive (C), the amino group in compound (A) and the carboxyl group in acid (C-1) form an ionic bond, thereby suppressing the aggregation caused by the association of compound (A) and crosslinking agent (B). In more detail, it is speculated that the interaction (e.g., electrostatic interaction) between the ammonium ion derived from the amino group in compound (A) and the carboxyl ion derived from the carboxyl group in acid (C-1) is stronger than the interaction between the ammonium ion derived from the amino group in compound (A) and the carboxyl ion derived from the carboxyl group in crosslinking agent (B), so aggregation can be suppressed. In addition, the present invention is not limited by any of the above speculations.

[0219] The acid (C-1) is not particularly limited as long as it is a compound having a carboxyl group and a weight average molecular weight of 46 to 195, and examples thereof include monocarboxylic acid compounds, dicarboxylic acid compounds, hydroxydicarboxylic acid compounds, etc. More specifically, examples of the acid (C-1) include formic acid, acetic acid, malonic acid, oxalic acid, citric acid, benzoic acid, lactic acid, glycolic acid, glyceric acid, butyric acid, methoxyacetic acid, ethoxyacetic acid, phthalic acid, terephthalic acid, picolinic acid, salicylic acid, and 3,4,5-trihydroxybenzoic acid.

[0220] In the present disclosure, the content of the acid (C-1) in the solution containing the material for forming the organic material layer, that is, the composition for forming the organic material layer, is not particularly limited. For example, the ratio (COOH / N) of the number of carboxyl groups in the acid (C-1) to the number of all nitrogen atoms in the compound (A) is preferably 0.01 to 10, more preferably 0.02 to 6, and even more preferably 0.5 to 3.

[0221] Base (C-2) is a base having a weight average molecular weight of 17 or more and 120 or less having nitrogen atoms. It is speculated that the composition for forming an organic material layer includes a base (C-2) as an additive (C), so that the carboxyl group in the crosslinker (B) forms an ionic bond with the amino group in the base (C-2), thereby suppressing the aggregation caused by the association of the compound (A) and the crosslinker (B). In more detail, it is speculated that the interaction between the carboxyl ion derived from the carboxyl group in the crosslinker (B) and the ammonium ion derived from the amino group in the base (C-2) is stronger than the interaction between the ammonium ion derived from the amino group in the compound (A) and the carboxyl ion derived from the carboxyl group in the crosslinker (B), so aggregation can be suppressed. In addition, the present invention is not limited by any of the above speculations.

[0222] The base (C-2) is not particularly limited as long as it is a compound having a nitrogen atom and a weight average molecular weight of 17 to 120 without a ring structure, and examples thereof include monoamine compounds, diamine compounds, etc. More specifically, examples of the base (C-2) include ammonia, ethylamine, ethanolamine, diethylamine, triethylamine, ethylenediamine, N-acetylethylenediamine, N-(2-aminoethyl)ethanolamine, and N-(2-aminoethyl)glycine.

[0223] In the present disclosure, the content of the base (C-2) in the composition for forming an organic material layer is not particularly limited. For example, the ratio of the number of nitrogen atoms in the base (C-2) to the number of carboxyl groups in the cross-linking agent (B) (N / COOH) is preferably greater than 0.5 and less than 5, and more preferably greater than 0.9 and less than 3.

[0224] In the case where the organic material layer of the substrate laminate of the present disclosure is required to be insulating, in order to improve the insulating property or mechanical strength, tetraethoxysilane, tetramethoxysilane, bis(triethoxysilyl)ethane, bis(triethoxysilyl)methane, bis(methyldiethoxysilyl)ethane, 1,1,3,3,5,5-hexaethoxy-1,3,5-trisilacyclohexane, 1,3,5,7-tetramethyl-1,3,5,7-tetrahydroxycyclosiloxane, 1,1,4,4-tetramethyl-1,4-diethoxydisilylethylene, 1,3,5-trimethyl-1,3,5-trimethyl-1,3,5-triethoxy-1,3,5-trisilacyclohexane can be mixed. Furthermore, in order to improve the hydrophobicity of the organic material layer with insulating properties, methyltriethoxysilane, dimethyldiethoxysilane, trimethylethoxysilane, etc. can also be mixed. These compounds can be mixed in order to control the etching selectivity.

[0225] The composition for forming an organic material layer may contain a solvent other than the polar solvent (D), and examples thereof include n-hexane.

[0226] In addition, for example, in order to improve electrical characteristics, the composition for forming an organic material layer may contain phthalic acid, benzoic acid, or the like, or derivatives thereof.

[0227] In order to suppress, for example, copper corrosion, the composition for forming an organic material layer may contain benzotriazole or a derivative thereof.

[0228] The pH of the composition for forming an organic material layer is not particularly limited, but is preferably 2.0 or more and 12.0 or less.

[0229] In addition, when an acid (C-1) is used as the additive (C), it is preferred to mix a mixture of the acid (C-1) and the compound (A) with the crosslinking agent (B). That is, it is preferred to mix the compound (A) and the acid (C-1) in advance before mixing the compound (A) and the crosslinking agent (B). Thus, when the compound (A) and the crosslinking agent (B) are mixed, the turbidity and gelation of the composition for forming an organic material layer can be appropriately suppressed (if gelation occurs, it sometimes takes time for the composition to become transparent, which is not preferred).

[0230] In addition, when a base (C-2) is used as the additive (C), it is preferred to mix a mixture of the base (C-2) and the crosslinking agent (B) with the compound (A). That is, it is preferred to pre-mix the crosslinking agent (B) and the base (C-2) before mixing the compound (A) and the crosslinking agent (B). Thus, when the compound (A) and the crosslinking agent (B) are mixed, the turbidity and gelation of the composition for forming an organic material layer can be appropriately suppressed (if gelation occurs, it sometimes takes time for the composition to become transparent, which is not preferred).

[0231] As a method for imparting an organic material layer-forming composition on the surface of a substrate having an electrode, for example, vapor deposition polymerization, CVD (chemical vapor deposition) method, ALD (atomic layer deposition) method and other vapor phase film forming methods, immersion method, spray method, spin coating method, rod coating method and other coating methods can be cited. When imparting an organic material layer-forming composition by a coating method, it is preferred to impart the aforementioned organic material layer-forming composition. For example, in the case of forming a film having a film thickness of micrometer size, it is preferred to use a rod coating method, and in the case of forming a film having a film thickness of nanometer size (several nm to hundreds of nm), it is preferred to use a spin coating method.

[0232] In addition, the film thickness of the composition for forming an organic material layer may be appropriately adjusted according to the desired thickness of the organic material layer.

[0233] For example, there is no particular limitation on the method of applying the composition for forming an organic material layer by spin coating. For example, the following method can be used: while rotating the substrate with a spin coater, the composition for forming an organic material layer is dripped onto the surface of the substrate having the electrode, and then the rotation speed of the substrate is increased to dry it.

[0234] In the method of applying the composition for forming an organic material layer by spin coating, there are no particular restrictions on the conditions such as the rotation speed of the substrate, the amount and time of dripping the composition for forming an organic material layer, the rotation speed of the substrate during drying, etc., and they can be appropriately adjusted in consideration of the thickness of the organic material layer formed, etc.

[0235] The substrate to which the organic material layer forming composition is applied may be cleaned to remove excess organic material layer forming composition applied. Examples of the cleaning method include wet cleaning using a rinse liquid such as a polar solvent, plasma cleaning, and the like.

[0236] After the composition for forming an organic material layer is applied to the substrate, energy such as heating is applied to cure the resin material and the like contained in the composition for forming an organic material layer, thereby forming an organic material layer.

[0237] When forming the organic material layer, energy is applied under the condition that the curing rate of the organic material layer including the resin and the resin precursor becomes less than 100%. This is because by making the curing rate of the organic material layer less than 100%, the formed organic material layer has a strength to withstand the grinding in the subsequent step B, and by heating in the subsequent step C, the reaction of the unreacted resin precursor proceeds, and it is expected that the curing rate will increase and the thickness of the organic material layer will change.

[0238] The curing rate of the organic material layer in the substrate laminate having the organic material layer and the electrode prepared in step A is preferably 60% or more, more preferably 70% or more, and further preferably 80% or more. The curing rate of the organic material layer in the substrate laminate prepared in step A is less than 100%, and may be 98% or less, 95% or less, or 90% or less. It should be noted that the curing rate of the organic material layer referred to here is the curing rate of the organic material layer before step B of forming the organic material layer and performing grinding, and is the curing rate before performing step C.

[0239] The method for measuring the curing rate will be described in detail in the step C described later.

[0240] <Grinding Step B>

[0241] Step B is a step of polishing the surface having the organic material layer in the substrate laminate having the organic material layer and the electrode prepared in step A. The surface has the organic material layer.

[0242] By performing step B, the organic material layer on the electrode is removed, and the electrode in the substrate laminate can be exposed. The polishing method for removing the organic material layer imparted to the electrode surface can be applied to a known method, such as a fly knife cutting method, a chemical mechanical polishing method (CMP), a plasma dry etching method, etc. The polishing method can be used alone or in combination of two or more methods.

[0243] Specifically, for example, in the fly cut method, a surface planer (DFS8910 (manufactured by DISCO Co., Ltd.)) or the like can be used. When CMP is used, as the slurry, for example, a slurry containing silicon dioxide or aluminum oxide, which is generally used for polishing resins, a slurry containing hydrogen peroxide and silicon dioxide, which is used for polishing metals, etc. can be used. When plasma dry etching is used, carbon fluorine plasma, oxygen plasma, etc. can also be used.

[0244] When polishing is performed in step B, the organic material layer on the surface of the electrode is removed by polishing, and the electrode is exposed. When the polishing rate of the organic material layer is slower than that of the copper constituting the electrode, the thickness of the organic material layer in the substrate laminate after polishing may become larger relative to the distance from the substrate to the top surface of the electrode (the thickness of the electrode), and in this case, a height difference is generated between the electrode and the organic material layer.

[0245] Figure 1 (C) is a schematic cross-sectional view showing a state after the substrate stack prepared in step A is polished.

[0246] exist Figure 1 In the example shown in (C), the thickness of the electrode 14 and the organic material layer 16 are reduced by polishing, and the electrode 14 made of copper, which is softer than the organic material layer 16, is polished to be larger, and the electrode 14 becomes concave.

[0247] It should be noted that, for the electrode exposed by removing the organic material layer, the oxide on the electrode surface can be reduced as needed. As the reduction treatment method, there are methods of heating the substrate at 100°C to 300°C in an acid atmosphere such as formic acid, and methods of heating the substrate in a hydrogen atmosphere. The above-mentioned reduction treatment can be carried out simultaneously with step E described later.

[0248] The surface of the organic material layer is planarized by polishing in step B. That is, in the polishing method, the surface of the organic material layer is planarized by performing at least one of a fly knife dicing method and a chemical mechanical polishing (CMP) method.

[0249] When the first substrate laminate after step B is bonded to the second substrate laminate in step D1 or step D2 described later, the surface roughness (Ra) of the organic material layer is preferably 1.2 nm or less. In addition, the Ra of the electrode is preferably 10.0 nm or less, more preferably 5 nm or less, and further preferably 1.0 nm or less.

[0250] The surface roughness of the organic material layer can be evaluated by morphological observation using a scanning probe microscope (SPM). Specifically, the surface roughness is determined by measuring a 3 μm×3 μm square area using a SPA400 (manufactured by Hitachi High-Technologies Corporation) as an SPM in a dynamic force microscope mode.

[0251] The surface of the polished substrate laminate can be cleaned as needed. Examples of the cleaning method include wet cleaning using a rinse solution, plasma cleaning, and the like. From the perspective of easy conduction, examples include dry cleaning using nitrogen plasma, oxygen plasma, atmospheric pressure plasma, and wet cleaning using citric acid, oxalic acid, formic acid, dilute sulfuric acid, alkaline cleaning solutions, and the like. By performing these treatments, not only can the particles on the resin be removed, but also the oxide film on the electrode can be removed, making it easy to obtain conduction.

[0252] <Step C of Heating the Substrate Laminated Body Polished in Step B>

[0253] In step C, the substrate laminated body polished in step B is heated. The curing reaction of the organic material layer proceeds by heating, the curing rate further increases, and the thickness of the organic material layer becomes thinner than before step C is performed.

[0254] The heating temperature is appropriately selected according to the organic material such as resin contained in the composition for forming an organic material layer formed on the substrate. Generally, it is preferred to heat at a temperature higher than the curing temperature of the organic material such as resin.

[0255] More specifically, the heating temperature is preferably 100°C to 450°C, more preferably 150°C to 450°C, and further preferably 180°C to 400°C.

[0256] Regarding the selection of organic materials such as resins contained in the organic material layer, the thickness of the organic material layer during step C is preferably 105% or less, and more preferably 100% or less of the thickness of the organic material layer before step C.

[0257] Here, "film thickness when step C is implemented" refers to the film thickness of the organic material layer at the moment when the surface temperature of the organic resin layer reaches the heating temperature predetermined in step C. That is, relative to the film thickness of the organic material layer before step C is implemented, the film thickness at the moment when the surface of the organic material layer reaches the predetermined heating temperature is preferably +5% or less, and more preferably 0% or less.

[0258] It should be noted that, for example, as described above, in the present disclosure, the height difference between the electrode and the organic material layer in the substrate stack after implementing process C is specified. Here, "the film thickness of the organic material layer after implementing process C" refers to the film thickness of the organic material layer after it is restored to room temperature by being left to cool after implementing process C. In this respect, it is different from the above-mentioned "film thickness when implementing process C".

[0259] The film thickness of the organic material layer when the step C is performed is the film thickness measured when the surface temperature of the organic material layer reaches a predetermined heating temperature.

[0260] When the organic material layer satisfies the above conditions, thermal expansion of the resin contained in the organic material layer can be easily eliminated by curing shrinkage, and the contact between the electrodes during the step C is further promoted.

[0261] From the same viewpoint, the resin contained in the organic material layer preferably has a tan δ value of 0.1 or less, more preferably 0.05 or less, as measured by dynamic viscoelasticity at the heating temperature in step C.

[0262] By using a resin having a tan δ value of 0.1 or less obtained by dynamic viscoelasticity measurement at the heating temperature in performing step C, the flow of the organic material layer forming composition containing the resin can be suppressed, and positional deviation of the formed organic material layer can be more effectively suppressed.

[0263] The dynamic viscoelasticity at the heating temperature in step C can be measured by a known method for measuring the dynamic viscoelasticity of a self-supporting film or a known method for measuring the dynamic nanoindentation of a film formed on a substrate such as Si.

[0264] When heating is performed in step C, step D1 of laminating with the second substrate laminate described later is first performed, and when heating is performed thereafter, the first substrate laminate polished in step B and the second substrate laminate may be overlapped and pressurized. In this case, the pressure during pressurization in step D1 is not particularly limited.

[0265] For example, regarding the pressure when mechanically pressurizing the substrates by overlapping two or more substrate stacks, in order to suppress the peeling of the insulating layer, it is preferably 0.1 MPa or more in step C, step D1 and step D2 described later, and preferably 10 MPa or less, more preferably 5 MPa or less, and further preferably 1 MPa or less.

[0266] According to the method for producing a substrate stack of the present disclosure, even when two or more substrate stacks are stacked and pressed at a relatively low pressure, the generation of voids at the electrode interface can be more effectively suppressed.

[0267] Pressurization can be performed simultaneously with heating.

[0268] As the pressurizing device, for example, a vacuum pressurizing reflow device "VPF200" manufactured by Shinapex, a wafer bonding machine XB8 manufactured by SUSSMicroTec, or the like can be used.

[0269] In addition, regarding the atmospheric pressure as a pressurization condition, when two or more substrate stacks are temporarily fixed in the step D1 or the step D2 described later, the absolute pressure is preferably greater than 10 -3 When two or more substrate stacks are heated and fixed in step C, the absolute pressure is preferably 10 -3 In order to facilitate the bonding of a plurality of substrate stacks, the absolute pressure is preferably 10 -3 Pa or more and 1MPa or less.

[0270] The heating in step C can be performed by a common method using a furnace or a hot plate. As the furnace, for example, SPX-1120 manufactured by Apex Corporation, VF-1000LP manufactured by Koyo Thermo System Co., Ltd., etc. can be used.

[0271] The heating in step C may be performed in an air atmosphere or in an inert gas (nitrogen, argon, helium, etc.) atmosphere. From the viewpoint of suppressing oxidation of the metal electrode, it is preferably performed in an inert gas atmosphere, and more preferably in a nitrogen atmosphere.

[0272] The heating time in step C is not particularly limited, and is, for example, 3 hours or less, and preferably 1 hour or less. The lower limit of the heating time is not particularly limited, and can be, for example, 5 minutes.

[0273] In order to shorten the heating time in step C, the composition for forming an organic material layer applied to the surface of the substrate may be irradiated with ultraviolet light (UV) in advance. As ultraviolet light, ultraviolet light with a wavelength of 170nm to 230nm, excimer light with a wavelength of 222nm, excimer light with a wavelength of 172nm, etc. are preferred. It is also one of the preferred methods to irradiate ultraviolet light in an inert gas atmosphere.

[0274] In the step A, when an organic material layer is formed on a substrate having an electrode, a composition for forming an organic material layer is applied to the substrate. The curing rate of the organic material layer in the substrate laminate having an organic material layer and an electrode prepared in the step A is less than 100%, and by heating in the step C, a curing reaction proceeds, and the curing rate of the organic material layer in the substrate laminate prepared in the step A is improved.

[0275] [Method for measuring curing rate]

[0276] The curing rate of the organic material layer in the present disclosure can be confirmed by measuring the peak intensity of specific bonds and structures in the organic material layer using FT-IR (Fourier transform infrared spectroscopy). Examples of the specific bonds and structures include bonds and structures generated by a crosslinking reaction.

[0277] For example, when an amide bond, an imide bond, a siloxane bond, a tetralin structure, an oxazole ring structure, etc. are formed in the organic material layer, or when a cross-linked structure generated by ring-opening polymerization of an epoxy group is formed, it can be determined that the organic material has been cured. Based on the organic material contained in the composition for forming the organic material layer, the peak intensity of the target bond, structure, etc. can be measured and confirmed by FT-IR.

[0278] The amide bond can be detected by -1 and about 1520cm -1 The presence of the vibration peak is confirmed.

[0279] The imide bond can be detected by -1 and about 1720cm -1 The presence of the vibration peak is confirmed.

[0280] Siloxane bonds can be detected through 1000 cm -1 ~1080cm -1 The presence of the vibration peak between them is confirmed.

[0281] The structure of tetralin can be seen at 1500 cm -1 The presence of the vibration peak between them is confirmed.

[0282] The oxazole ring structure can be seen at about 1625 cm -1 and about 1460cm -1 The presence of the vibration peak is confirmed.

[0283] The ring-opening reaction of epoxy groups can be seen at 910 cm -1 This is confirmed by the reduction of the vibration peak.

[0284] From the viewpoint of heat resistance, the organic material layer in the substrate laminate of the present invention preferably has at least one of a siloxane bond or an imide bond. From the viewpoint of enabling temporary fixation at room temperature, the organic material layer particularly preferably has a siloxane bond.

[0285] The curing rate of the organic material layer after step C can also be confirmed as follows: in the composition for forming the organic material layer before being applied to the substrate, the joint before performing step C, and the organic material layer after performing step C, the peak intensity of specific bonds and structures is measured by FT-IR (Fourier transform infrared spectroscopy) (when there are multiple peaks such as imide and amide, it is the sum of these peak intensities), and the increase or decrease rate of the peak intensity is calculated. It should be noted that in the case of a band-shaped peak that is difficult to separate peaks such as a siloxane bond, the maximum peak intensity can be used for confirmation.

[0286] As a method for measuring the curing rate of the organic material layer after performing step C, specifically, when a specific bond and structure are generated by the curing reaction, the increase rate of the peak intensity can be calculated by the following formula, and the calculated value can be used as the curing rate of the organic material layer.

[0287] Increase rate of peak intensity (curing rate of organic material layer) = [(peak intensity of specific bonds and structures of organic material layer before step C) / (peak intensity of specific bonds and structures of organic material layer after heating under heating conditions of step C)] × 100

[0288] In addition, the background signal can be removed by a common method. In addition, the FT-IR measurement can be performed by a transmission method or a reflection method as needed.

[0289] In the above-mentioned rate of increase of peak intensity, when there are a plurality of bonds or structures causing an increase in peak intensity, the peak intensity may be replaced with the total intensity of the plurality of peak intensities.

[0290] From the perspective of more appropriately suppressing the generation of voids caused by outgassing generated during the curing shrinkage of the organic material layer, the curing rate of the organic material layer after the step C is preferably 50% or more, more preferably 70% or more, further preferably 80% or more, particularly preferably 90% or more, and further preferably 93% or more. The curing rate of the organic material layer after the step C may be 100%, 99% or less, 95% or less, or 90% or less. It should be noted that the curing rate of the organic material layer referred to here is the curing rate after the step B of preparing a substrate having an electrode and an organic material layer and performing grinding of the organic material layer and after the step C is performed.

[0291] Note that the heating step C may be performed before the step of bonding the first substrate stack and the second substrate after the step B described later (ie, step D1) or after the step B described later (ie, step D2).

[0292] Figure 1 (D) is a schematic cross-sectional view showing the substrate laminate after the step C is performed. Figure 1 In (D), the curing rate of the organic material layer 16 is increased by heating in step C, resulting in shrinkage of the thickness of the organic material layer 16. Figure 1 Compared with (C), the height difference between the organic material layer 16 and the electrode 14 ( Figure 2 (b) is further zoomed out.

[0293] The height difference between the organic material layer 16 and the electrode 14 before and after the step C is performed will be described in more detail.

[0294] The height difference between the organic material layer and the electrode in the substrate laminate after the step C is performed is preferably not less than -100 nm and not more than 200 nm.

[0295] Furthermore, it is preferred that the height difference between the organic material layer and the electrode in the substrate laminate before the step C is implemented is greater than -100nm and less than 0nm, and the height difference between the organic material layer and the electrode in the substrate laminate after the step C is implemented is greater than 0nm and less than 150nm. Further, it is preferred that the height difference between the organic material layer and the electrode in the substrate laminate before the step C is greater than -50nm and less than 0nm, and the height difference between the organic material layer and the electrode in the substrate laminate after the step C is implemented is greater than 0nm and less than 100nm. More preferably, it is greater than -20nm and less than 0nm, and it is preferred that the height difference between the organic material layer and the electrode in the substrate laminate after the step C is implemented is greater than 0nm and less than 50nm.

[0296] In other words, after implementing process B and before implementing process C, the height difference between the organic material layer and the electrode may be a depression of the electrode. From the viewpoint of suppressing the generation of voids, it is preferred that the height difference is suppressed by heating in process C so that the interface between the organic material layer and the electrode is consistent, that is, the height difference is 0 nm, or the electrode is slightly convex relative to the organic material layer.

[0297] Here, when the thickness of the electrode on the surface of the substrate stack having the electrode is set to b1 and the thickness of the organic material layer is set to b2, the height difference is expressed as [b1-b2], and a negative height difference indicates that the thickness of the electrode is smaller than the thickness of the organic material layer.

[0298] The thickness of the organic material layer in the substrate laminate is not particularly limited, and can be, for example, 0.01 μm to 8.0 μm, preferably 0.03 μm to 6.0 μm, and more preferably 0.05 μm to 5.0 μm. By making the thickness of the adhesive layer 0.01 μm or more, the bonding strength between the substrate laminate and the second substrate etc. can be improved. By making the thickness of the organic material layer 8.0 μm or less, when the organic material layer is formed on a large-area substrate, the deviation of the thickness of the organic material layer can be more effectively suppressed.

[0299] The amount of silicon in the surface of the organic material layer is preferably 0.1 atm% to 20 atm%, and if the content of silicon atoms is within the above range, sufficient bonding strength to the substrate can be ensured. The content of silicon atoms is preferably 0.5 atm% to 15 atm%, and more preferably 0.5 atm% to 10 atm%.

[0300] The amount of silicon in the surface of the organic material layer can be evaluated by atomic ratio measurement using an X-ray photoelectron spectrometer (XPS). Specifically, when the total amount of the four most elements detected in the wide spectrum (binding energy 50eV to 950eV) is set to 100%, the amount of silicon can be determined based on the ratio of the peak intensity, i.e., Si, in the Si2p narrow spectrum (binding energy 95eV to 110eV) corresponding to silicon. As an XPS device, for example, AXIS-NOVA (manufactured by KRATOS) can be used.

[0301] In the surface of the organic material layer, the ratio of the number of oxygen atoms to the number of silicon atoms (O / Si) is preferably 1 or more. When the ratio of the number of oxygen atoms to the number of silicon atoms is 1 or more, there is a tendency for the adhesion to the substrate to become higher. The ratio of the number of oxygen atoms to the number of silicon atoms (O / Si) is preferably 1.5 or more, more preferably 2 or more. From the viewpoint of reducing water absorption, the ratio of the number of oxygen atoms to the number of silicon atoms (O / Si) is preferably 20 or less, more preferably 15 or less.

[0302] In the surface of the organic material layer, the content of nitrogen atoms is preferably 0.1 atm% to 20 atm%. When the content of nitrogen atoms is within the above range, when the substrate contains metal, there is a tendency for the adhesion with the substrate to become higher. The content of nitrogen atoms is preferably 2 atm% to 15 atm%, more preferably 5 atm% to 10 atm%.

[0303] The silicon atom content, nitrogen atom content, and ratio of the number of oxygen atoms to the number of silicon atoms in the organic material layer can be measured using an X-ray photoelectron spectrometer (XPS).

[0304] The silicon atom content can be measured based on the peak intensity in a narrow spectrum corresponding to silicon (binding energy 95eV to 110eV), that is, Si, and the nitrogen atom content can be measured based on the peak intensity in a narrow spectrum corresponding to nitrogen (binding energy 390eV to 410eV), that is, N.

[0305] The ratio of the number of oxygen atoms to the number of silicon atoms can be measured by O / Si based on the ratio of the peak intensity in a narrow spectrum corresponding to oxygen (binding energy 525 eV to 540 eV), i.e., O, to the peak intensity in a narrow spectrum corresponding to silicon (binding energy 95 eV to 110 eV), i.e., Si.

[0306] It should be noted that the silicon atom content, the nitrogen atom content, and the ratio of the number of oxygen atoms to the number of silicon atoms can also be measured by other elemental analysis methods such as energy dispersive X-ray analysis (EDX).

[0307] When the laminate is heated during the implementation of step C, outgassing generated during the curing and shrinkage of the organic material layer may cause the generation of undesirable voids as described above.

[0308] The laminate is preferably at 10 -7 The degassing pressure measured in an environment of Pa becomes 10 -5 The temperature above 400°C is 400°C or higher. When the temperature is 400°C or higher, the decrease in bonding strength due to outgassing tends to be suppressed. -5 The temperature above 400°C is preferably 420°C or above, more preferably 450°C or above. -5 The upper limit of the temperature above Pa is not particularly limited, and may be, for example, 600° C. or lower, or 550° C. or lower.

[0309] The laminate is 10 -7 The outgassing pressure measured under an environment of 100 Pa can be measured by the following method.

[0310] The Si substrate with the organic material layer formed thereon was cut into 10 mm × 10 mm squares to prepare a sample for outgassing measurement. The sample for outgassing measurement was used to measure the outgassing amount by heating using EMD-WA1000S manufactured by ESCO. The atmospheric pressure (base pressure) was set to 10 -7 Pa, and the heating rate was set to 30°C / min. As the surface temperature of the silicon substrate, a standard sample (H + Silicon injection, CaC2O4 dripping, Ar + The outgassing peak of the silicon wafer was measured and the temperature of the thermocouple under the workbench was calibrated.

[0311] The temperature is raised and the degassing pressure is calculated to be 1×10 -5 The temperature of Pa.

[0312] In the organic material layer, the content of the inorganic or resin filler having a maximum diameter of 0.3 μm or more is preferably 30% by mass or less, more preferably 10% by mass or less, and even more preferably 0% by mass, based on the entire organic material layer.

[0313] When the content of the filler contained in the organic material layer is within the above range, poor bonding of the laminate can be suppressed even when the thickness of the organic material layer is reduced. In addition, when obtaining a multi-layer substrate laminate, when the substrate laminate having the organic material layer is mixed and bonded to the second substrate laminate, sometimes alignment is performed by mechanically recognizing the alignment marks formed on each substrate. When the content of the filler is within the above range, the transparency of the organic material layer is improved, and more accurate alignment can be performed using the alignment marks.

[0314] From the perspective of appropriately suppressing the generation of voids both before and after the heating treatment of the substrate laminate in step C, the composite elastic modulus of the organic material layer at 23°C is preferably 20 GPa or less, more preferably 10 GPa or less. In addition, from the perspective of appropriately suppressing the misalignment of the alignment, the composite elastic modulus of the bonding portion of the substrate laminate at 23°C is preferably 0.1 GPa or more, more preferably 1 GPa or more, both before and after the heating treatment in step C.

[0315] The composite elastic modulus can be measured using a nanoindenter (trade name TI-950Tribo Indenter, manufactured by Hysitron, Berkovich-type indenter) by measuring the unloading-displacement curve at 23°C at a test depth of 20 nm. The composite elastic modulus at 23°C can be calculated from the maximum load and maximum displacement according to the calculation method of the reference (Handbook of Micro / nano Tribology (Second Edition), edited by Bharat Bhushan, CRC Press).

[0316] The complex elastic modulus is defined by the following formula (1): In formula (1), Er represents the complex elastic modulus, Ei represents the Young's modulus of the indenter, which is 1140 GPa, νi represents the Poisson's ratio of the indenter, which is 0.07, and Es and νs represent the Young's modulus and Poisson's ratio of the sample, respectively.

[0317] [Number 1]

[0318]

[0319] The organic material layer preferably contains sodium and potassium at a content of 10 ppb or less on an element basis. If the sodium or potassium content is 10 ppb or less on an element basis, the occurrence of defects in the electrical characteristics of the semiconductor device, such as malfunction of the transistor, can be suppressed.

[0320] From the aspect of improving the close adhesion of the second substrate class joined in the process D1 or process D2 described later, the organic material layer formed on the substrate preferably has a functional group that can form a chemical bond on the surface of the organic material layer. As such a functional group, for example, amino, epoxy, vinyl, silanol (Si-OH group) etc. can be cited, and from the aspect of heat resistance, epoxy and silanol are preferred. These functional groups can be formed by surface treatment after the formation and grinding of the organic material layer, or can be formed by silane coupling agent treatment, etc. Alternatively, the organic material layer can also contain compounds containing these functional groups.

[0321] The organic material layer preferably has Si-OH groups on the surface. By making the surface of the organic material layer have Si-OH groups, when the first substrate laminate is joined to the second substrate, it is easy to achieve temporary fixation of the two at low temperature. Furthermore, by heating and pressurizing treatment after temporary fixation, the bonding strength of the interface can be further increased.

[0322] Whether the surface of the organic material layer has Si-OH groups can be evaluated by surface analysis of the organic material layer based on time-of-flight secondary ion mass spectrometry (TOF-SIMS). Specifically, using PHInanoTOFII (ULVAC-PHI Co., Ltd.) as TOF-SIMS, it is possible to evaluate whether the surface of the organic material layer has Si-OH groups based on the presence or absence of a peak with a mass-to-charge ratio (m / Z) of 45.

[0323] <Thermal Linear Expansion Coefficient in the Thickness Direction of the Organic Material Layer>

[0324] The coefficient of thermal linear expansion (hereinafter also referred to as CTE) of the organic material layer in the substrate laminate of the present disclosure in the thickness direction is preferably not less than -10 ppm / K and not more than 150 ppm / K.

[0325] The CTE of the organic material layer can be measured by the following method.

[0326] The resin was formed into a film on a Si substrate and cured at 300°C for 1 hour. Then, the sample was heated from 30°C to 300°C in a nitrogen atmosphere using an ellipsometer with a stage heating mechanism (manufactured by Japan Semilab Co., Ltd.) to measure the film thickness expansion of the organic material layer.

[0327] The CTE was calculated from the film thickness expansion using the following formula.

[0328] CTE = [(film thickness at 300°C) - (film thickness at 30°C)] / (film thickness at 30°C) / 270K

[0329] The CTE of the organic material layer is preferably not less than -10 ppm / K and not more than 150 ppm / K, more preferably not more than 60 ppm / K, and further preferably not more than 30 ppm / K.

[0330] Examples of resins whose CTE easily falls within the above-mentioned preferred range include resins having an elastic modulus of 10 GPa or less at room temperature (25°C) (for example, polyimide, polybenzoxazole, epoxy resin, resin containing siloxane, etc.), resins having SiOH groups on the bonding surface, resins having a Si content of 0.1 amt% to 20 amt% in the organic material layer, and resins containing siloxane bonds.

[0331] In the method for producing a substrate stack of the present disclosure, the surface energy of the interface of the bonding portion in the substrate stack after the step D1 and before the step C is preferably 0.05 J / m 2 As described above, the surface energy of the interface of the bonding portion in the substrate laminate after the step C is preferably more than 1 J / m 2 , more preferably 2.5 J / m 2 above.

[0332] The surface energy (bonding strength) of the bonding interface between the first substrate stack and the second substrate etc. can be determined by a blade insertion test according to the method of non-patent document MP Maszara, G. Goetz, A. Cavigila and JB Mckitterick, Journal of Applied Physics, 64 (1988) 4943-4950.

[0333] A blade with a thickness of 0.1 mm to 0.3 mm is inserted into the interface of the bonding portion of the substrate stack after step D1 and before step C, or after step D1 and after step C, and the distance of the substrate stack peeling from the blade tip is measured using an infrared light source and an infrared camera. Then, the surface energy can be calculated based on the following formula.

[0334] γ=3×10 9 ×t b 2 ×E 2 ×t 6 / (32×L 4 ×E×t 3 )

[0335] Here, γ represents the surface energy (J / m 2 ), t b represents the thickness of the blade (m), E represents the Young's modulus (GPa) of the substrates such as the silicon substrate included in the first substrate stack and the second substrate, t represents the thickness of the substrate in the first substrate stack and the substrate in the second substrate, etc. (m), and L represents the peeling distance of the stack from the tip of the blade (m).

[0336] <Glass Transition Temperature of Organic Material Layer>

[0337] The glass transition temperature of the organic material layer included in the first insulating layer is preferably 150° C. or higher, more preferably 180° C. or higher.

[0338] The glass transition temperature of the organic material layer can be controlled by selecting the resin component contained in the organic material layer.

[0339] The glass transition temperature of the organic material layer can be measured by the following method.

[0340] First, the composition for forming an organic material layer was applied onto the resin film with a gap of 250 μm using an applicator, and baked at 200° C. for 1 hour in a nitrogen atmosphere to cure the composition to form a film. Next, the cured film was peeled off from the resin film.

[0341] The film obtained above was used for measurement using a DSC measuring apparatus Discovery X3 DSC (manufactured by TA Instruments). The first glass transition temperature from room temperature to 400° C. was determined from the DSC thermogram as the glass transition temperature of the organic material layer.

[0342] <Step D1 and Step D2 of Obtaining a Multilayer Substrate Laminate>

[0343] The method for manufacturing a substrate of the present disclosure may further include the step of bonding the first substrate laminate obtained through step B to a second substrate or another laminate to obtain a multi-layer substrate laminate. The step of obtaining a multi-layer substrate laminate may be performed on the substrate laminate before or after the aforementioned step C.

[0344] Hereinafter, the process of joining the substrate stack before implementing the aforementioned process C to a second substrate or other stack to obtain a multi-layer substrate stack will be referred to as process D1, and the process of joining the substrate stack after implementing process C to a second substrate or other stack to obtain a multi-layer substrate stack will be referred to as process D2.

[0345] From the viewpoint of reducing the number of times of step C and minimizing the total step time, the step of obtaining a multi-layer substrate stack is preferably step D1 performed on the substrate stack before step C is performed.

[0346] In step D1, for example, the first substrate stack obtained in step B is brought into contact with and bonded to the second substrate or the second substrate stack, thereby obtaining a multi-layer substrate stack.

[0347] The step of obtaining a multi-layer substrate laminate may be performed by performing step C as follows: Figure 1 As shown in (D), after reducing the height difference between the electrode 14 and the organic material layer 16, the electrode 14 is brought into contact with the second substrate, etc., and a bonding step D2 is performed; or first, as shown in Figure 1 As shown in (C), the substrate laminate in which the organic material layer 16 protrudes relative to the electrode 14 is brought into contact with the second substrate or the like, and then step C is performed to shrink the organic material layer 16 to perform a bonding step D1.

[0348] When the substrate laminate having undergone step B is brought into contact with another laminate, it is preferred that the organic material layers of both laminates be bonded to each other.

[0349] Figure 3 2 is a schematic cross-sectional view showing a state where a substrate laminate after step C is bonded to another laminate after step D1. Figure 3 In the process, the substrate laminate 10 having the electrode 14 and the organic material layer 16 on one surface of the substrate 12 after the implementation of step C is bonded to the other laminate 24. The other laminate 24 has the electrode 20 and the organic material layer 22 on one surface of the substrate 18. The substrate laminate 10 and the other laminate 24 are bonded in the following state: the electrode 14 of the substrate laminate 10 is in contact with the electrode 20 of the other laminate 24, and the organic material layer 16 of the substrate laminate 10 is in contact with the organic material layer 22 of the other laminate 24, thereby suppressing the generation of gaps between the electrodes.

[0350] When the first substrate stack is bonded to the second substrate etc. to obtain the substrate stack, a step of temporarily fixing the first substrate stack after overlapping the second substrate etc. may be further included before performing step C. The first substrate stack may be temporarily fixed to the second substrate etc. and then heated in step C to bond them.

[0351] The temporary fixing of the first substrate stack and the second substrate and the like is preferably performed at a low temperature of room temperature or higher and 100° C. or lower.

[0352] The temporary fixing of the first substrate stack and the second substrate is preferably performed at an absolute pressure of 10 -3 Pa or more and 10MPa or less.

[0353] In order to suppress peeling of the insulating layer during temporary fixing of the first substrate stack and the second substrate, the pressure during mechanical pressing is preferably 0.1 MPa or more and preferably 10 MPa or less, more preferably 5 MPa or less, and further preferably 1 MPa or less.

[0354] The second substrate or substrate stack joined to the first substrate stack 10 may have an insulating layer on the joining surface. The insulating layer preferably includes at least one selected from a resin and an inorganic material, and more preferably includes at least one selected from an inorganic material.

[0355] The material of the inorganic material included in the insulating layer is not particularly limited, for example, as long as it is the material of the inorganic material used when the inorganic materials are bonded to each other on the semiconductor substrate. Specifically, the inorganic material can include at least one element selected from the group consisting of Si, Al, Ti, Zr, Hf, Fe, Ni, Cu, Ag, Au, Ga, Ge, Sn, Pd, As, Pt, Mg, In, Ta and Nb, preferably at least one element selected from the group consisting of Si, Ga, Ge and As. The inorganic material may include oxides, carbides, nitrides, etc. of the elements. More specifically, SiO2, SiCN, SiN, SiOC, etc. can be cited.

[0356] It should be noted that, when step C is implemented after step D1 is implemented to obtain a substrate stack, the pressurization conditions when heating the substrate stack in step C can be any one of reduced pressure and increased pressure, but in the present disclosure, the substrate stack can be heated below 10 MPa, and the substrate stack is preferably heated at atmospheric pressure or reduced pressure.

[0357] The pressure under reduced pressure during the heating process is 1×10 -6 The range of Pa to 0.05MPa. It has the following advantages: by heating under atmospheric pressure or reduced pressure, the bonding of multiple substrate stacks with chips can be processed together, and further, by processing multiple substrate stacks together in an oven, the process time can be shortened. In addition, the heating in step C can be carried out in an atmospheric atmosphere or in an inert gas (nitrogen, argon, helium, etc.) atmosphere. Among them, from the viewpoint of suppressing the oxidation of the metal electrode, it is preferably carried out in an inert gas atmosphere, and more preferably in a nitrogen atmosphere.

[0358] For example, the first substrate stack may be bonded to the second substrate. Figure 4 It is a schematic cross-sectional view showing a state where the substrate stack 10 , that is, the substrate stack having the electrode 14 and the organic material layer 16 on one surface of the substrate 12 , is bonded to the second substrate 26 .

[0359] Figure 4 Although a substrate stacked body in which a first substrate stacked body and a second substrate stacked body are bonded together is shown, bonding of the first substrate stacked body and the second substrate etc. is not limited thereto.

[0360] In addition, for example, the first substrate stack is a semiconductor substrate, the second substrate stack is a semiconductor chip, and the process D1 is a process of bonding two or more of the semiconductor chips on the first semiconductor substrate to obtain a multi-layer substrate stack. After the multi-layer substrate stack is obtained by implementing the process D1, in the process C, the multi-layer substrate stack obtained in the process D1 is heated to be joined, thereby manufacturing the multi-layer substrate stack.

[0361] In the step D1, for example, the second substrate stack may be a semiconductor chip having an electrode on one surface and an electrode on the other surface.

[0362] Regarding the manufacturing method disclosed in the present invention, in the step D1, two or more semiconductor chips having an electrode on one surface and an electrode on the other surface are bonded to the substrate stack, i.e., the semiconductor substrate, which has been ground in the step B to obtain a multilayer substrate stack. Then, in the step C, the multilayer substrate stack that has undergone the step D1 is heated, and the step D1 and the step C are performed more than twice.

[0363] Figure 5 It is a schematic cross-sectional view showing a state in which a plurality of semiconductor chips are bonded to the surface of a second substrate 26 .

[0364] It should be noted that in Figure 1 , Figure 3 to Figure 5 In the illustrated embodiment, the substrate laminate 10 as a semiconductor chip has the electrode 14 and the organic material layer 16 on one surface of the substrate 12 , but the substrate laminate may also have an electrode on the other surface of the substrate.

[0365] That is, a semiconductor chip as another laminated body may have an electrode on one surface and an electrode on the other surface.

[0366] Fig. 6A and Figure 6B This is a schematic cross-sectional view showing an example of a semiconductor chip which is a substrate laminate having electrodes on both surfaces of a substrate.

[0367] Fig. 6A The substrate laminate 30 shown is a schematic cross-sectional view showing an example of a semiconductor chip having an electrode (hereinafter, also referred to as a through electrode) 28 that penetrates the substrate 12. For example, in the substrate laminate 30, by having a through electrode 28 that reaches from one surface of the substrate 12 to the other surface, the substrate laminate 30 has electrodes on both surfaces of the substrate 12.

[0368] Figure 6B The substrate laminate 32 shown includes electrodes 14 on one surface and the other surface of the substrate 12 , and further includes a through electrode 28 extending from the one surface to the other surface of the substrate 12 .

[0369] It should be noted that Fig. 6A and Figure 6B The example of the method in which electrodes are provided on both surfaces of the substrate is shown, but the method in which electrodes are provided on both surfaces of the substrate is not limited to Fig. 6A and Figure 6B The method shown.

[0370] Figure 7 This is a schematic cross-sectional view showing an example of a state in which a plurality of semiconductor chips having electrodes on both surfaces are bonded to a wafer serving as a second substrate.

[0371] exist Figure 7 In the substrate laminate shown, two semiconductor chips 32 having electrodes 28 penetrating the substrate 12 are bonded to the wafer 26. The size of the wafer 26, the arrangement position and number of semiconductor chips 32 bonded to the wafer 26 can be appropriately selected according to the purpose of the substrate laminate.

[0372] Alternatively, the step of bonding the second substrate to the first substrate stack may be performed two or more times to further stack a plurality of substrate stacks.

[0373] It is also possible to have the following step D2 and the following step C, and to have the step D2 and the step C more than twice, wherein in the step D2, two or more semiconductor chips having an electrode on one surface and also having an electrode on the other surface are bonded to the substrate stack, i.e., the semiconductor substrate, which has been ground in the step B to obtain a substrate stack, and in the step C, the substrate stack that has undergone the step D2 is heated.

[0374] Figure 8 This is a schematic cross-sectional view showing an example of a state in which a plurality of semiconductor chips having electrodes on both surfaces are bonded to a wafer as a semiconductor substrate, and another semiconductor chip having electrodes on both surfaces is further stacked on the bonded semiconductor chips.

[0375] exist Figure 8 In the illustrated substrate laminate, a semiconductor chip 32 is bonded to a wafer 26 , and a second semiconductor chip 32 is further bonded to the semiconductor chip 32 bonded to the wafer 26 .

[0376] In this way, by stacking a plurality of semiconductor chips 32 on the wafer 26 , the semiconductor chips can be stacked vertically to form a multi-layer three-dimensional structure, thereby achieving high integration of the substrate stack.

[0377] It should be noted that the preferred material of the second substrate, etc. is the same as the preferred material of the first substrate laminate. The second substrate, etc. joined to the first substrate laminate may be the same as or different from the substrate laminate. In addition, when a plurality of substrate laminates are stacked and joined to a substrate, etc., the materials and layer structures of the joined substrate laminates may be the same as or different from each other.

[0378] <Other Processes>

[0379] The method for producing a substrate laminate of the present disclosure may include other steps as necessary in addition to the above-mentioned step A, step B, step C, step D1, and step D2.

[0380] Examples of the other steps include the above-mentioned pressurizing step, the below-mentioned surface treatment step, the below-mentioned thinning step, and the like.

[0381] (Surface treatment process)

[0382] The method for producing a substrate stacked body disclosed in the present disclosure may include, as another step, a surface treatment step of forming a functional group on a surface where the first substrate stacked body and the second substrate etc. are in contact.

[0383] The surface treatment step may be performed on a surface of at least one of the first substrate stack and the second substrate, etc., which is in contact with both, preferably on a surface of the first substrate stack which is in contact with the second substrate stack.

[0384] The surface treatment step is a step of forming at least one functional group selected from the group consisting of hydroxyl, epoxy, carboxyl, amino and mercapto groups on the surface of at least one of the substrate laminate and the second substrate, etc., on the contacting side of the two (hereinafter also referred to as "surface treatment step").

[0385] Examples of the surface treatment include plasma treatment, chemical treatment, and ozone treatment such as UV ozone treatment.

[0386] The hydroxyl groups can be provided on the surfaces of the first substrate and the second substrate respectively by subjecting the surfaces of the first substrate and the second substrate to surface treatment such as plasma treatment, chemical treatment, or ozone treatment such as UV ozone treatment.

[0387] The hydroxyl group is preferably present in a state of being bonded to at least one element selected from the group consisting of Si, Al, Ti, Zr, Hf, Fe, Ni, Cu, Ag, Au, Ga, Ge, Sn, Pd, As, Pt, Mg, In, Ta and Nb contained in the first substrate or the second substrate. Among them, the surface of the organic material layer or the like on the side forming the bonding portion of at least one of the substrates more preferably has a silanol group containing a hydroxyl group.

[0388] The epoxy groups can be provided on the surfaces of the first substrate and the second substrate, respectively, by subjecting the surfaces of the first substrate and the second substrate to surface treatment such as silane coupling using epoxy silane.

[0389] The carboxyl groups can be provided on the surfaces of the first substrate and the second substrate, respectively, by subjecting the surfaces of the first substrate and the second substrate to surface treatment such as silane coupling using carboxyl silane.

[0390] The amino group can be provided on the surfaces of the first substrate and the second substrate, respectively, by subjecting the surfaces of the first substrate and the second substrate to surface treatment such as silane coupling using aminosilane.

[0391] The mercapto groups can be provided on the surfaces of the first substrate and the second substrate, respectively, by subjecting the surfaces of the first substrate and the second substrate to surface treatment such as silane coupling using mercaptosilane.

[0392] In addition, from the viewpoint of improving the bonding strength of the substrate stack, a primer film of a silane coupling agent or the like may be formed on at least one surface of the first substrate stack and the second substrate.

[0393] (Thinning Processing)

[0394] The method for manufacturing a substrate stack of the present disclosure may perform thinning processing (back grinding or back grinding) on ​​at least one of the first substrate stack and the second substrate as necessary after step C, step D1 or step D2.

[0395] (Cutting Processing)

[0396] The method for manufacturing a substrate laminate of the present disclosure may be performed after the above step C, after the step D1, or after the step D2, and the substrate may be singulated to produce semiconductor chips as required. For example, the dicing process may be performed using a blade dicing machine (e.g., DAD6340 (manufactured by DISCO Corporation)), a plasma dicing machine, a stealth dicing machine, etc.

[0397] 〔Semiconductor devices〕

[0398] The semiconductor device disclosed in the present invention comprises a first substrate stack and a second substrate stack, wherein the first substrate stack comprises a first substrate, an electrode on the first substrate, and a first insulating layer, and the second substrate stack comprises a second substrate, an electrode on the second substrate, and a second insulating layer. An organic material layer is provided on one surface of the first substrate stack, and at least one of the first insulating layer and the second insulating layer is a layer composed of an inorganic material. In the insulating layers of the first substrate stack and the second substrate stack, the total thickness of the organic material layers in the insulating layers including the layers composed of inorganic materials is greater than 1 / 20 and less than 1 / 3 of the total thickness of the insulating layers including the layers composed of inorganic materials, and the organic material layer serving as the first insulating layer is directly bonded to the second insulating layer.

[0399] The semiconductor device disclosed herein can easily reduce the difference between the expansion and contraction of the electrode and the expansion and contraction of the insulating layer when repeatedly subjected to heating and cooling (i.e., heat shock resistance test), thereby preventing the electrode from breaking. Therefore, relative to the total thickness of the insulating layer of the first substrate stack and the insulating layer of the second substrate stack, the total thickness of the organic material layer in the insulating layer of the first substrate stack and the insulating layer of the second substrate stack is preferably greater than 1 / 20 and less than 1 / 3.

[0400] This is because, by setting the above-mentioned structure, if the insulating layer includes an organic material layer whose thermal linear expansion coefficient (CTE) is several times larger than that of electrode materials such as copper, internal stress is generated in the direction of peeling off the joined electrode due to the difference in CTE between the organic material layer and the electrode material during heating or cooling, and disconnection of the joined electrode can be suppressed. From the same point of view, the total thickness of the organic material layer in the insulating layer of the first substrate laminate and the insulating layer of the second substrate laminate is more preferably 1 / 20 or more and 1 / 4 or less, more preferably 1 / 20 or more and 1 / 6 or less, and more preferably 1 / 10 or more and 1 / 6 or less, relative to the total thickness of the insulating layer of the first substrate laminate and the insulating layer of the second substrate laminate.

[0401] Here, the total thickness of the insulating layer of the first substrate stack and the insulating layer of the second substrate stack refers to the total thickness of each insulating layer in the insulating layer of the first substrate stack and the insulating layer of the second substrate stack, and the total thickness of the organic material layer in the insulating layer of the first substrate stack and the second substrate stack refers to the total thickness of the organic material layer possessed by at least any one of the insulating layers of the insulating layer of the first substrate stack and the second substrate stack.

[0402] The semiconductor device disclosed in the present invention can easily reduce the difference between the expansion and contraction of the electrode and the expansion and contraction of the insulating layer when repeatedly heated and cooled (heat shock test), thereby preventing the electrode from breaking. Therefore, it is preferred that the first insulating layer is an insulating layer having a two-layer structure of a layer composed of an inorganic material and a layer of an organic material, the first substrate stack has a first substrate, a layer composed of an inorganic material, and an organic material layer in sequence, and the second insulating layer is a layer composed of an inorganic material, that is, a single-layer insulating layer.

[0403] In addition, by setting the above structure, the total thickness of the organic material layers in the insulating layer of the first substrate stack and the insulating layer of the second substrate stack can be easily set to be greater than 1 / 20 and less than 1 / 3 of the total thickness of the insulating layer of the first substrate stack and the insulating layer of the second substrate stack.

[0404] (Example of the laminated structure of substrate laminate)

[0405] Examples of laminate structures in various applications of substrate laminates obtained by the method for producing substrate laminates disclosed herein are shown below. It should be noted that the bonding layer in the laminate structures exemplified below refers to a layer in a bonded state comprising at least one selected from the group consisting of inorganic materials and resins.

[0406] For MEMS packaging; Si / bonding layer / Si, SiO2 / bonding layer / Si, SiO2 / bonding layer / SiO2, Cu / bonding layer / Cu,

[0407] For microfluidics: PDMS / bonding layer / PDMS, PDMS / bonding layer / SiO2,

[0408] For CMOS image sensors; SiO2 / junction layer / SiO2, Si / junction layer / Si, SiO2 / junction layer / Si, for through silicon vias (TSV); SiO2 (with Cu electrode) / junction layer / SiO2 (with Cu electrode), Si (with Cu electrode) / junction layer / Si (with Cu electrode),

[0409] For optical devices; (InGaAlAs, InGaAs, InP, GaAs) / bonding layer / Si,

[0410] For LED; (InGaAlAs, GaAs, GaN) / joining layer / Si, (InGaAlAs, GaAs, GaN) / joining layer / SiO2, (InGaAlAs, GaAs, GaN) / joining layer / (Au, Ag, Al), (InGaAlAs, GaAs, GaN) / joining layer / sapphire.

[0411] The method for producing a substrate laminate of the present disclosure enables lamination at low pressure by a simple method and effectively suppresses poor conduction caused by gaps between electrodes and in the joints between the substrate and the electrodes, and is therefore useful in producing high-density circuits.

[0412] Example

[0413] Hereinafter, the method for manufacturing a substrate laminate and a semiconductor device of the present disclosure will be specifically described by way of examples, but the present disclosure is not limited to these examples.

[0414] Hereinafter, ultrapure water (Milli-Q water manufactured by Millipore Corporation, with a resistance of 18 MΩ·cm (25° C.) or less) was used as “water”.

[0415] Each evaluation was performed by the following method.

[0416] <Cross-linked structure>

[0417] The crosslinked structure of the bonding layer was measured by FT-IR (Fourier transform infrared spectroscopy). The analysis device used was as follows.

[0418] ~FT-IR analysis equipment~

[0419] Infrared absorption analysis device (DIGILAB Excalibur (manufactured by DIGILAB))

[0420] ~Measurement conditions~

[0421] IR light source: air-cooled ceramic,

[0422] Beam splitter: Wide range KBr,

[0423] Detector: Peltier cooled DTGS,

[0424] Measurement wave number range: 7500cm -1 ~400cm -1 ,

[0425] Resolution: 4cm -1 ,

[0426] Total times: 256,

[0427] Background: Using Si bare wafers,

[0428] Measurement atmosphere: N2 (10L / min),

[0429] IR (infrared) incident angle: 72° (= Brewster angle of Si)

[0430] ~Judgment conditions~

[0431] The imide bond is detected at 1770 cm -1 、1720cm -1 The siloxane bond is determined by the presence of a vibration peak at 1000 cm -1 ~1080cm -1 The amide bond is determined by the presence of vibration peaks between 1650cm -1 、1520cm -1 It is judged by the presence of vibration peak.

[0432] <Measurement of surface roughness (Ra)>

[0433] The measurement was performed in a 3 μm×3 μm square area using a scanning probe microscope (SPM) SPA400 (manufactured by Hitachi High-Technologies Corporation) in a dynamic force microscopy mode.

[0434] <Measurement of complex elastic modulus>

[0435] For the measurement samples prepared in each embodiment and each comparative example, a nanoindenter (trade name TI-950Tribo Indenter, manufactured by Hysitron, Berkovich type indenter) was used to measure the unloading-displacement curve at 23°C under the condition of a test depth of 20 nm, and the composite elastic modulus at 23°C was calculated from the maximum load and maximum displacement according to the calculation method of the reference (Handbook of Micro / nanoTribology (2nd edition), edited by Bharat Bhushan, CRC Press).

[0436] It should be noted that the "elastic modulus after complete curing" in the table means the "complex elastic modulus".

[0437] In addition, the complex elastic modulus is defined by the following formula (1). In the formula (1), Er represents the complex elastic modulus, Ei represents the Young's modulus of the indenter, which is 1140 GPa, νi represents the Poisson's ratio of the indenter, which is 0.07, and Es and νs represent the Young's modulus and Poisson's ratio of the sample, respectively.

[0438] [Number 1]

[0439]

[0440] Furthermore, the complex elastic modulus of the organic material layer after complete curing at 200° C. was measured by the following method. The results are also shown in Table 1.

[0441] The complex elastic modulus of the organic material layer at 200° C. was determined in the same manner as the above-mentioned method for measuring the complex elastic modulus of the organic material layer at 23° C., except that the temperature of the organic material layer was set to 200° C. by heating the stage.

[0442] <Measurement of water drop contact angle>

[0443] The static contact angle of water was measured under the conditions of 23° C. and 50% humidity using a solid-liquid interface analysis system (Drop Master 500 image processing system, manufactured by Kyowa Interface Science Co., Ltd.).

[0444] <Calculation of curing rate>

[0445] The formed bonding layer was subjected to FT-IR measurement before and after heating at 300° C. for 1 hour, and the curing rate was calculated by the above formula.

[0446] <Measurement of Silicon Amount on the Surface of Organic Material Layer>

[0447] Using the X-ray photoelectron spectrometer (XPS) AXIS-NOVA (manufactured by KRATOS), when the total amount of the four most detected elements in the wide spectrum (binding energy 50eV to 950eV) is set to 100%, the amount of silicon on the surface of the organic material layer in the joint is measured based on the ratio of the peak intensity, i.e., Si, in the Si2p narrow spectrum (binding energy 95eV to 110eV) equivalent to silicon.

[0448] The silicon atom content, nitrogen atom content, and ratio of the number of oxygen atoms to the number of silicon atoms in the organic material layer were measured using an X-ray photoelectron spectrometer (XPS) AXIS-NOVA (manufactured by KRATOS Corporation).

[0449] The silicon atom content is measured based on the peak intensity in a narrow spectrum corresponding to silicon (binding energy 95 eV to 110 eV), that is, Si, and the nitrogen atom content is measured based on the peak intensity in a narrow spectrum corresponding to nitrogen (binding energy 390 eV to 410 eV), that is, N.

[0450] Regarding the ratio of the number of oxygen atoms to the number of silicon atoms, O / Si was measured using an X-ray photoelectron spectrometer (XPS) AXIS-NOVA (manufactured by Kratos) based on the ratio of the peak intensity in a narrow spectrum corresponding to oxygen (binding energy 525 eV to 540 eV), i.e., O, to the peak intensity in a narrow spectrum corresponding to silicon (binding energy 95 eV to 110 eV), i.e., Si.

[0451] <Evaluation of the Presence or Absence of Silanol Groups on the Surface of the Adhesive Layer>

[0452] Whether or not the surface of the bonding layer has Si—OH groups was evaluated based on the presence or absence of a peak with a mass-to-charge ratio (m / z) of 45 using time-of-flight secondary ion mass spectrometry (TOF-SIMS) PHI nanoTOFII (ULVAC-PHI Co., Ltd.).

[0453] <Conductivity of the Bonding Layer>

[0454] The conductivity in the bonding layer was evaluated by the resistance value.

[0455] The resistance value of the daisy chain was measured by a two-terminal method by bringing a probe for measuring electrical characteristics into contact with the external terminal of the bottom chip.

[0456] As a resistance value measuring device, a digital ultra-high resistance / micro current meter 5451A manufactured by AGENCY was used.

[0457] When the resistance value per Cu-Cu joint was less than 10Ω, it was evaluated as a level without practical problems (A grade), and when it was 10Ω or more per Cu-Cu joint, it was evaluated as a level with practical problems (B grade).

[0458] The measurement was performed at four locations on one substrate laminate, and the arithmetic mean value was used for evaluation.

[0459] <Measurement of surface energy>

[0460] According to the method of non-patent document MP Maszara, G. Goetz, A. Cavigila and JB Mckitterick, Journal of Applied Physics, 64 (1988) 4943-4950., the surface energy (bonding strength) of the interface of the joint of a multilayer temporarily fixed substrate stack or the obtained multilayer substrate stack is measured by a blade insertion test.

[0461] A blade with a thickness of 0.1 mm to 0.3 mm is inserted into the interface of the joint of a multi-layer temporarily fixed substrate stack or a multi-layer substrate stack, and the distance that the stack or substrate stack is peeled off from the blade tip is measured using an infrared light source and an infrared camera. Then, the surface energy is measured based on the following formula.

[0462] γ=3×10 9 ×t b 2 ×E 2 ×t 6 / (32×L 4 ×E×t 3 )

[0463] Here, γ represents the surface energy (J / m 2 ), t b represents the thickness of the blade (m), E represents the Young's modulus of the silicon substrate included in the first substrate and the second substrate (GPa), t represents the thickness of the first substrate and the second substrate (m), and L represents the peeling distance of the stack or substrate stack from the blade tip (m).

[0464] [Example 1]

[0465] <Preparation of a Solution Containing a Material for Forming an Organic Material Layer (Organic Material Layer Forming Composition)>

[0466] A composition for forming an organic material layer was prepared. The details are as follows.

[0467] As an organic material, 50% by mass of 3-aminopropyldiethoxymethylsilane (3APDES) and 50% by mass of water were mixed, 45g of solution A containing a hydrolyzate of 3APDES, 33.79g of solution B containing 70% by mass of oxydiphthalic acid half ester (Y in formula (B-2) is O and R is ethyl) and 30% by mass of ethanol, 20g of 1-propanol and 1.21g of water were mixed to prepare a composition for forming an organic material layer.

[0468] <Substrate Preparation>

[0469] Chips with Cu electrodes (10 μm Φ, 6 μm thick, daisy pattern) manufactured by WALTS were prepared (top chip: WALTS-TEGCC40-0101JY, bottom chip: WALTS-TEGIP40-0101JY).

[0470] Here, the Cu electrode was formed by a semi-additive method in a 1.2 μm-thick P-TEOS film (PE-TEOS / plasma TEOS) on which the through-electrode was formed so as to bury the through-electrode.

[0471] <Formation of Organic Material Layer>

[0472] Place the substrate prepared as described above on a spin coater in such a manner that the surface on which the Cu electrode is formed faces upward in the vertical direction, and drop 2.0 mL of the prepared composition for forming an organic material layer at a certain speed for 10 seconds. After holding for 13 seconds, rotate at 2000 rpm (rpm is the rotation speed per minute) for 1 second, rotate at 600 rpm for 30 seconds, and then rotate at 2000 rpm for 10 seconds to dry. Thus, the composition for forming an organic material layer is imparted to the substrate. Heat the substrate to which the composition for forming an organic material layer is imparted at 150°C for 1 hour in a nitrogen atmosphere. Thus, an organic material layer (thickness 5 μm) having a siloxane bond and an imide bond is formed, and a substrate laminate having an electrode and an organic material layer is obtained. [Process A]

[0473] <Calculation of curing rate>

[0474] The organic material layer formed on the Si substrate by the same method as above was subjected to FT-IR measurement after applying the composition for forming the organic material layer and heating at 150° C. for 1 hour. For the imide bond, the above formula was used to determine the -1 The curing rate was calculated based on the peak intensity of , and the result was that the curing rate was 70%.

[0475] In addition, in Example 3, the curing rate was calculated from the change in peak intensity before and after the step C was performed.

[0476] <Polishing of Organic Material Layer>

[0477] Using a CMP device (RDP-500 (manufactured by Fujikoshi Machinery Co., Ltd.)), using COMPOL80 (manufactured by FUJIMI INCORPORATED CO., LTD.), chemical mechanical polishing (CMP) is performed on the surface of the substrate on which the organic material layer is formed, thereby removing the organic material layer on the electrode to expose the electrode containing copper, and the substrate after CMP is cleaned with a post-CMP cleaning liquid (MCX-2005 (manufactured by Mitsubishi Chemical Corporation)). [Step B]

[0478] The thickness of the organic material layer in the region without electrode formation after CMP was 4000 nm (c), and the surface roughness (Ra) of the organic material layer was 0.40 nm to 0.80 nm (described in Table 1). In addition, the Ra of the copper electrode was 4.6 to 8.0 nm (described in Table 1).

[0479] An atomic force microscope (AFM device: E-sweep (manufactured by SII NanoTechnology), cantilever Si, DFM mode) was used to measure the height difference between the organic material layer and the exposed electrode. The result showed that the electrode was recessed by 80nm (top chip) to 250nm (bottom chip) compared to the surface of the resin (b) (described in Table 1).

[0480] <Manufacturing of Substrate Laminate>

[0481] Using a blade cutter, the substrate on which the organic material layer has been polished as described above is singulated into chips with a top chip of 7.3 mm×7.3 mm and a bottom chip of 10.0 mm×10.0 mm. In order to remove foreign matter on the surface, the singulated chips are subjected to CMP again using COMPOL80, and after being cleaned with MCX-2005, they are immersed in a 1 mass % aqueous solution of citric acid for 1 minute to remove the copper oxide film. Using a chip loader, the top chip and the bottom chip are bonded to each other at room temperature (25°C) while aligning the positions of the electrodes using the alignment marks formed on the chip. The bonding conditions are pressurization at 0.2 MPa for 1 second in the atmosphere at room temperature. [Process D1]

[0482] The bonded semiconductor chips were heated under pressure at 300°C and 5 MPa for 0.5 hours in a nitrogen atmosphere (oxygen concentration <10 ppm, atmospheric pressure) using a wafer bonder (manufactured by SUSS MicroTec, XB-8) to produce a multi-layer substrate laminate formed by bonding two substrates. [Step C]

[0483] For the substrate stack after implementing process B, process D1 is not performed. It is heated at 300°C in a nitrogen atmosphere (oxygen concentration <10ppm, atmospheric pressure) for 0.5 hours, and the height difference between the organic material layer and the electrode is measured after returning to room temperature. The result shows that the electrode is concave by 80nm (bottom chip) to convex by 90nm (top chip) compared to the surface of the resin (a).

[0484] The value calculated by substituting the height difference and the film thickness of the organic material layer into the following formula (1) is 0.0425, which is within the range of 0.001 to 0.500 specified in the present invention.

[0485] Top chip: (90-(-80 during <formation of organic material layer>)) / 4000=0.0425

[0486] That is, the curing shrinkage ratio is 0.0425.

[0487] [Example 2]

[0488] The substrate laminate of Example 2 was produced in the same manner as in Example 1 except that the substrate used in Example 1 was changed to a substrate having a Cu electrode of a bottom chip (WALTS-TEGIP40-0101JY) manufactured by WALTS Corporation changed to 10 μm Φ 6 μm thick.

[0489] The obtained substrate laminate was evaluated in the same manner as in Example 1.

[0490] [Example 3]

[0491] On the base chip substrate used in Example 1, a P-TEOS film was further formed by plasma CVD to form a layer (TEOS film) composed of an inorganic material.

[0492] Then, the 3-aminopropyldiethoxymethylsilane (3APDES; (3-Aminopropyl)diethoxymethylsilane) contained in the organic material layer forming composition used in Example 1 was changed to 3-aminopropyltriethoxysilane (APTES; (3-Aminopropyl)triethoxymethylsilane), and an organic material layer (Resin 2) with a thickness of 2.5 μm was formed on the surface of the TEOS layer in the same manner as in Example 1.

[0493] In step A, the heating conditions were set to a nitrogen atmosphere, 200° C., and 1 hour.

[0494] In step B, both the top chip and the bottom chip were polished by COMPOL80 (manufactured by FUJIMIN CORPORATION) until the Cu electrode was exposed, and then polished by Lk393c4 (manufactured by NITTA DuPont Corporation) to adjust the height difference of Cu.

[0495] In step C, the heating conditions were set to a nitrogen atmosphere (oxygen concentration <10 ppm, atmospheric pressure), 350° C., and 0 MPa for 1.5 hours.

[0496] A substrate laminate of Example 3 was produced in the same manner as in Example 1 except for the above.

[0497] The total thickness of the layer composed of inorganic material and the layer composed of organic material of the top chip was 1.7 μm (1.2 μm for the layer composed of inorganic material and 0.5 μm for the layer composed of organic material), and the thickness of the layer composed of inorganic material of the bottom chip was 1.2 μm.

[0498] The obtained substrate laminate was evaluated in the same manner as in Example 1.

[0499] Fig. 9 A schematic cross-sectional view of a substrate laminate of Example 3 is shown. The substrate laminate of Example 3 is a laminate of a first substrate laminate 40 and a second substrate laminate 50, wherein the first substrate laminate 40 has a layer (insulating layer) 36 made of an inorganic material and an electrode 38 on a first substrate 34, and the second substrate laminate 50 has an insulating layer and an electrode having a two-layer structure of a layer 44 made of an inorganic material and a layer 46 of an organic material on a second substrate 42, wherein the layer 36 made of an inorganic material is directly bonded to the organic material layer 46. Fig. 9 The second substrate stack 50 is the top chip, Fig. 9 The first substrate stack 40 in the embodiment is the bottom chip.

[0500] [Comparative Example 1]

[0501] In Example 1, except that the heating conditions in <Formation of Organic Material Layer> were changed from 150° C. for 1 hour to 300° C. for 1 hour, a substrate laminate of Comparative Example 1 was produced in the same manner as in Example 1 and evaluated in the same manner as in Example 1.

[0502] [Comparative Example 2]

[0503] In Example 2, except that the heating conditions in <Formation of Organic Material Layer> were changed from 150° C. for 1 hour to 300° C. for 1 hour, a substrate laminate of Comparative Example 1 was produced in the same manner as in Example 2 and evaluated in the same manner as in Example 1.

[0504] The evaluation results are shown in Table 1 below.

[0505] In addition, in the following Table 1, the thickness of the Cu electrode in the substrate laminate is equal to the total thickness of the insulating layers such as the organic material layer and the layer composed of the inorganic material in the top chip and the bottom chip.

[0506] [Table 1]

[0507]

[0508] According to the results in Table 1, the substrate laminates obtained by the manufacturing methods of Examples 1 to 3 all satisfy the conditions specified by the above formula (1). According to the evaluation results, good conduction at the joint is obtained, and the conductivity is at a level that is not a problem in practical use. According to the results of Example 3, by satisfying the above formula (1) in at least the substrate laminate of the top chip, good conduction at the joint can be obtained.

[0509] In the substrate laminate obtained by the manufacturing method of Comparative Example 1, the curing rate of the organic material layer in the substrate laminate prepared in step A reached 100%, and even after heating in step C, the height difference of the interface between the electrode and the organic material layer did not decrease, and was outside the range specified by the above formula (1). As a result of evaluation, good conduction at a level without practical problems could not be obtained. This is considered to be caused by the generation of gaps in the joint.

[0510] Explanation of symbols

[0511] 10: substrate laminate (first substrate laminate), 12: substrate (first substrate), 14: electrode (first electrode), 16: organic material layer, 18: substrate (second substrate), 20: electrode (second electrode), 22: organic material layer, 24: substrate laminate (second substrate laminate), 26: substrate (wafer), 28: through-electrode, 30: substrate laminate, 32: substrate laminate (semiconductor chip), 34: substrate (first substrate), 36: layer composed of an inorganic material (insulating layer), 38: electrode (first electrode), 40: substrate laminate (first substrate laminate), 42: substrate (second substrate), 44: layer composed of an inorganic material (insulating layer), 46: organic material layer, 48: electrode (second electrode), 50: substrate laminate (first substrate laminate)

[0512] The disclosures of Japanese Patent Application No. 2022-122934 filed on August 1, 2022 and Japanese Patent Application No. 2023-018757 filed on February 9, 2023 are incorporated into the present disclosure by reference.

[0513] All documents, patent applications, and technical standards described in this disclosure are hereby incorporated by reference into this disclosure to the same extent as if each individual document, patent application, and technical standard was specifically and individually indicated to be incorporated by reference.

Claims

1. A method for manufacturing a substrate laminate, comprising: Step A, preparing a substrate laminate having a substrate, an electrode and an organic material layer, Step B, grinding the surface of the substrate stack having the organic material layer, and Step C, heating the substrate stack after being ground in step B; The organic material layer in the substrate laminate prepared in step A is provided on at least one surface of the substrate having an electrode, and the organic material layer contains a resin and a resin precursor and has a curing rate of less than 100%. When the height difference between the electrode and the organic material layer in the substrate laminate before the step C is performed is a, the height difference between the electrode and the organic material layer in the substrate laminate after the step C is b, and the film thickness of the organic material layer before the step C is c, a, b and c satisfy the following formula (1): [(ba) / c]=0.001~0.500 (1).

2. The method for manufacturing a substrate laminate according to claim 1, comprising: Step D1 is to obtain a multi-layered substrate stack by bonding the first substrate stack before step C and the second substrate stack having electrodes arranged on substrates after step B is performed.

3. The method for manufacturing a substrate laminate according to claim 1, comprising: In step D2, the first substrate stack after the step C is performed is joined to a second substrate stack having electrodes arranged on substrates to obtain a multi-layer substrate stack.

4. The method for producing a substrate laminate according to claim 2 or 3, wherein: The first substrate stack and the second substrate stack have at least one insulating layer, one of the insulating layers of the first substrate stack and the second substrate stack is a layer composed of inorganic material, and at least one of the surfaces of the first substrate stack and the second substrate stack is an organic material layer.

5. The method for manufacturing a substrate laminate according to claim 4, wherein: The total thickness of the organic material layers in the insulating layers of the first and second substrate stacks is 1 / 20 to 1 / 3 of the total thickness of the insulating layers of the first and second substrate stacks.

6. The method for manufacturing a substrate laminate according to claim 4, wherein: The insulating layer of the substrate laminate having an organic material layer on the surface has a layer composed of an inorganic material.

7. The method for manufacturing a substrate laminate according to claim 5, wherein: At least one of the surface of the first substrate stack and the surface of the second substrate stack is a layer composed of an inorganic material, and the organic material layer is bonded to the layer composed of the inorganic material.

8. The method for manufacturing a substrate laminate according to claim 4, wherein: The insulating layer of the first substrate laminate is an insulating layer having a two-layer structure of a layer composed of an inorganic material and a layer of an organic material. The first substrate laminate includes a first substrate, a layer composed of an inorganic material, and an organic material layer in this order.

9. The method for manufacturing a substrate laminate according to claim 8, wherein: The insulating layer of the second substrate laminate is a layer composed of an inorganic material, that is, a single-layer insulating layer.

10. The method for manufacturing a substrate laminate according to claim 2, wherein: After the step D1 is performed to bond the first substrate stack before the step C to the second substrate stack to obtain a multi-layered substrate stack, in the step C, the multi-layered substrate stack is heated under atmospheric pressure or reduced pressure.

11. The method for manufacturing a substrate laminate according to claim 2, wherein: The substrate stack is a semiconductor substrate, and the second substrate stack is a semiconductor chip. The step D1 is a step of bonding two or more semiconductor chips onto the semiconductor substrate to obtain a multi-layer substrate laminate. After the step D1 is performed to obtain a multi-layer substrate laminate, in the step C, the multi-layer substrate laminate obtained in the step D1 is heated.

12. The method for producing a substrate laminate according to claim 2 or 3, wherein: The second substrate laminate is a semiconductor chip having an electrode on one surface and an electrode on the other surface.

13. The method for manufacturing a substrate laminate according to claim 2, wherein: The second substrate laminate is a semiconductor chip having an electrode on one surface and an electrode on the other surface. In the step D1, two or more semiconductor chips each having an electrode on one surface and an electrode on the other surface are bonded to the substrate laminate, i.e., the semiconductor substrate, which has been polished in the step B to obtain a multilayer substrate laminate. In the step C, the multi-layer substrate stack that has undergone the step D1 is heated, and The method for manufacturing a substrate laminate includes performing the step D1 and the step C two or more times.

14. The method for producing a substrate laminate according to any one of claims 1 to 3, wherein: The height difference between the organic material layer and the electrode in the substrate laminate after the step C is greater than or equal to -100 nm and less than or equal to 200 nm. Here, when the thickness of the electrode on the surface of the substrate having the electrode is set to b1 and the thickness of the organic material layer is set to b2, the height difference is expressed as [b1-b2], and a negative height difference indicates that the thickness of the electrode is smaller than the thickness of the organic material layer.

15. The method for producing a substrate laminate according to any one of claims 1 to 3, wherein: The height difference between the organic material layer and the electrode in the substrate laminate before the step C is greater than -100 nm and less than 0 nm, and the height difference between the organic material layer and the electrode in the laminate after the step C is greater than 0 nm and less than 150 nm, Here, when the thickness of the electrode on the surface of the substrate having the electrode is set to b1 and the thickness of the organic material layer is set to b2, the height difference is expressed as [b1-b2], and a negative height difference indicates that the thickness of the electrode is smaller than the thickness of the organic material layer.

16. The method for manufacturing a substrate laminate according to claim 1, wherein: In the step C, the thickness of the organic material layer during the step C is 105% or less of the thickness of the organic material layer before the step C is performed.

17. A semiconductor device comprising: A first substrate laminate including a first substrate, an electrode on the first substrate, and a first insulating layer, and A second substrate laminate comprising a second substrate, an electrode on the second substrate, and a second insulating layer; An organic material layer is provided on one surface of the first substrate stack. At least one of the first insulating layer and the second insulating layer is a layer composed of an inorganic material, In the insulating layer of the first substrate stack and the insulating layer of the second substrate stack, the total thickness of the organic material layer in the insulating layer including the layer composed of the inorganic material is 1 / 20 or more and 1 / 3 or less of the total thickness of the insulating layer including the layer composed of the inorganic material, The organic material layer as the first insulating layer is directly bonded to the second insulating layer.

18. The semiconductor device according to claim 17, wherein: The second insulating layer includes a layer composed of an inorganic material.

19. The semiconductor device according to claim 18, wherein: The second insulating layer includes a layer made of an inorganic material, and the layer made of the inorganic material is provided on a surface of the second substrate laminate.

20. The semiconductor device according to claim 17, wherein The first insulating layer is an insulating layer having a two-layer structure of a layer composed of an inorganic material and a layer of an organic material. The first substrate laminate includes a first substrate, a layer composed of an inorganic material, and an organic material layer in this order.

21. The semiconductor device according to claim 20, wherein: The second insulating layer is a layer composed of an inorganic material, that is, a single-layer insulating layer.

22. The semiconductor device according to claim 17, wherein: The organic material layer included in the first insulating layer includes a resin containing a siloxane bond.

Citation Information

Patent Citations

  • JP1974033120B1

  • Connecting body for semiconductor substrate and its connection

    JP1992132258A

  • Alkylated polyethyleneimine derivative and its production

    JP1994016809A

  • Ethyleneimine polymer and its production method

    JP2001213958A

  • Semiconductor device and manufacturing method therefor

    JP2010226060A